Prioritizing emerging contaminants in tropical riverine systems: An integrated approach using ecological and human health risk indices - Muhammad Raznisyafiq Razak; Noraishah Mydin Abdul-Aziz; Singh Nisheljeet; Nawaltul Akma Ahmad Sabri; Muhammad Qusyairi Jori Roslan; Nor Rohaizah Jamil; Didi Erwandi Mohamad Haron; Pao-Chi Liao; Ahmad Zaharin Aris (Regulatory Toxicology and Pharmacology, 2026)

Potato residue chips as corn replacement in Angus bulls: Effects on carcass characteristics, meat quality, and serum metabolites - Chang-Xiao Shi; Hui-Li Wang; Ying-Qi Li; Muhammad Aziz-ur-Rahman; Si-Yu Zhang; Jia-Jie Deng; Wen-Xi Zhao; Xing-Yue Yi; Yi-Min Zhang; Yang He; Bing-hai Cao; Hua-Wei Su (Food and Humanity, 2026)

Comparative analysis of cow and buffalo milk based probiotic yoghurt formulations, for physicochemical, sensory, and in vitro biological activities - Muhammad Azhar Iqbal; Mian Anjum Murtaza; Aysha Sameen; Iram Hafiz; Ashiq Hussain; Tariq Aziz; Ashwag Shami; Nada K. Alharbi; Fahad Al-Asmari; Fakhria A. Al-Joufi (Food and Humanity, 2026)

How can new quality productivity affect energy poverty? Evidence from China - Xiong Liu; Shuxiang Li; Yuchi Li; Fengjing Zhu; Yutan Wu; Jintao Lu; Muhammad Aziz; Mingang Gao (Energy Policy, 2026)

Upregulation and diagnostic potential of Interleukin-36 cytokine isoforms in dilated cardiomyopathy: evidence from human and murine models - Alishba Kainat; Mubeen Tabish Nasim; Fazlul Aziz Mian; Syed Muhammad Nurulain; Hassaan Mehboob Awan; Tahir Iqbal; Sabir Hussain (Molecular Biology Reports, 2026)

Genome-wide characterization and comparative analysis of Bacillus paranthracis MBBL1 reveals genomic plasticity features - Nimra Hanif; Muhammad Naveed; Maida Salah Ud Din; Tariq Aziz; Ashwag Shami; Fakhria A. Al-Joufi (Functional & Integrative Genomics, 2026)

Numerical investigation of PCM-based thermal energy storage device of nuclear power plants containment using a fins configuration - Muhammad Adnan; Hui Wang; Yanlu Wang; Cao Xiaxin; Hailemichael Guadie Mengsitu; Arif Aziz; Jamil Khan (Annals of Nuclear Energy, 2026)

Emerging advanced technologies: Modulation of sensory properties in milk and whey systems – A review - Waris Aziz; Khawaja Muhammad Ali Tayyab; Tahir Mahmood Qureshi; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Trends in Food Science & Technology, 2026)

Exploring the bioactivity of Ageratum conyzoides L: Antioxidant, antimicrobial, and cytotoxic properties of flower extracts - Md. Safkat Zaman Fahim; Shyama Prosad Moulick; Sauda Sultana Mimi; Subarna Sandhani Dey; Md. Omar Sha Rafi; Sadia Afrin Chhanda; Dabashes Adhikery; Muhammad Mahfuz Hasan; Shahin Aziz; Tanvir Muslim (Next Research, 2026)

Finite element-based investigation and explainable machine learning prediction of moment resistance of steel flush end-plate connections - Md. Ibrahim Kholil; Muhammad Harunur Rashid; Aziz Ahmed; Md. Waliul Islam (Next Research, 2026)

Recent advances in nZVI@MOF composites for Cr(VI) removal: A comprehensive review - Safina Zafar; Shumaila Bibi; Mohamed H. Helal; Haider Ali; Guilherme Luiz Dotto; Zeinhom M. El-Bahy; Muhammad Ahmad Wattoo; Aziz ur Rehman (Journal of Environmental Chemical Engineering, 2026)

Advancing plastic waste-to-hydrogen: A cross-technology framework integrating eco-technoeconomic analysis, catalyst stability benchmarking and knowledge mapping - Usman Bello; Haruna Adamu; Muhammad Faizan; Abdul Aziz Jallow; Maryem Ourimi; Roa’a Alzoubi; Shafirah Samsuri; Abdul Gani Abdul Jameel; Mohammad Nahid Siddiqui (Journal of Environmental Chemical Engineering, 2026)

Engineering metal organic framework 808 and MXene Interfaces for sustainable oxygen evolution electrocatalysis in alkaline media - Shumaila Bibi; Syed Shoaib Ahmad Shah; Muhammad Irfan; Faiza Jan Iftikhar; Mohamed H. Helal; Muhammad Zahid Qureshi; Shu-Juan Bao; Aziz ur Rehman (Fuel, 2026)

Optimization of ohmic-assisted thermochemical pretreatment of empty fruit bunch for enhanced hydrogen production and fermentation kinetics - Izzah Farhana Ab Aziz; Hasfalina Che Man; Muhammad Hazwan Hamzah; Rozita Omar; Nur Syakina Jamali; Ibrahim B. Dalha (Biomass and Bioenergy, 2026)

Performance analysis of a helium-nitrogen binary gas mixture centrifugal compressor for terrestrial gas-cooled reactor power plants of closed Brayton cycles - Arif Aziz; Qun Zheng; Adil Malik; Muhammad Haris; Ghulam Ishaque; Shadman Ahmad Khattak (Annals of Nuclear Energy, 2026)

Germination-driven biochemical remodeling of cereals and pseudocereals: Impacts on nutrient bioaccessibility, phytochemical enrichment, and functional food potential - Djilali Benabdelmoumene; Muhammad Waqar; Abderahman Shawky; Omnia Darwish Askar; Wasim S.M. Qadi; Said Dahmouni; Mariam Gamaleldin; Faidruz Azura Jam; Ahmed Mediani; Hamizah Shahirah Hamezah; Habsah Aziz; Sajad Ali; et al. (Food Chemistry, 2026)

Corrigendum to “A review on biohydrogen production through dark fermentation via the lactate pathway” [Bioresour. Technol. 454 (2026) 134726] - Amir Izzuddin Adnan; Hassan Mohamed; Eqwan Roslan; Nur Atiqah Mohamad Aziz; Mouad Firah; Mohd Nur Ikhmal Salehmin; Bidattul Syirat Zainal; Muhammad Fikri Zulkornain; Farah Nurhikmah; Saifuddin Nomanbhay; Peer Mohamed Abdul; Sumaiya Zainal Abidin (Bioresource Technology, 2026)

Bimetallic ferro and lanthanum impregnated on nano HZSM-5 catalysts for the Reutealis trisperma oil hydroprocessing to rich aromatic jet fuel range - Muhammad Al Muttaqii; Abdul Aziz; Sugeng Priyanto; Indri Yati; Muh. Nur Khoiru Wihadi; Amalia Kurnia Amin; Kiky Corneliasari Sembiring; Hendris Hendarsyah Kurniawan; Sudibyo; Didik Prasetyoko; Reva Edra Nugraha; Lenny Marlinda; et al. (Bioresource Technology Reports, 2026)

Carbon Dots Derived from Food Waste for Environmental Contaminant Sensing: A Rreview - Kawan F. Kayani; Mohammed K. Rahim; Sewara J. Mohammed; Aso Q. Hassan; Muhammad S. Mustafa; Shujahadeen B. Aziz (Water, Air, & Soil Pollution, 2026)

Monitoring of insecticide resistance and associated fitness costs in diamondback moth, Plutella xylostella, (L.) (Lepidoptera: Plutellidae): Lesson from fields of Pakistan - Muhammad Shehzad; Muhammad Tariq; Muhammad Asif Aziz; Lu ZhaoZhi; Munir Ahmad (International Journal of Tropical Insect Science, 2026)

Comment on the use of participatory modelling to inform management of endemic foot-and-mouth disease - Mochammad Masrikhan; Muhammad Hilmy Aziz (Preventive Veterinary Medicine, 2026)

A review on biohydrogen production through dark fermentation via the lactate pathway - Amir Izzuddin Adnan; Hassan Mohamed; Eqwan Roslan; Nur Atiqah Mohamad Aziz; Mouad Firah; Mohd Nur Ikhmal Salehmin; Bidattul Syirat Zainal; Muhammad Fikri Zulkornain; Farah Nurhikmah; Saifuddin Nomanbhay; Peer Mohamed Abdul; Sumaiya Zainal Abidin (Bioresource Technology, 2026)

Spatiotemporal Distribution of Cyanobacteria in Tropical Freshwater Reservoir and Machine Learning Prediction using Explainable Artificial Intelligence - Muhammad Sarfraz Ahmad Mangat; Teh Sabariah binti Abd Manan; Sharifah Sakinah Syed Abd Mutalib; Zarimah Mohd Hanafiah; Nur Azwa Muhamad Bashar; Salmia Beddu; Nur Liyana Mohd Kamal; Daud Mohamad; Shatha Aser Hamad Aldala’in; Adel Gohari; Wan Hanna Melini Wan Mohtar; Muhammad Raza Ul Mustafa; et al. (Water, Air, & Soil Pollution, 2026)

Biological and synthetic biology strategies for polystyrene degradation: mechanisms, microbial advances, and circular economy perspectives - Mehar Nazir; Asma Rehman; Ahmad H. Ibrahim; Sawsan S. Al-Rawi; Manahil Akmal; Ghazala Iram; Faiza Manzoor; Sadia Aziz; Muhammad Shehroz Zafar; Muhammad Adnan Iqbal (Biodegradation, 2026)

Revolutionizing the potential of laccase from Bacillus paralicheniformis as an eco-friendly solution to reduce polychlorinated dibenzofurans contamination through integrated computational approach - Muhammad Naveed; Ayesha Saleem; Tariq Aziz; Urooj Rasheed; Arooj Azeem; Maryum Rasheed; Manal F. Elkhadragy; Ashwag Shami; Hanan Abdulrahman Sagini; Rewaa S. Jalal; Hayam A. Alwabsi; Fakhria A. Al-Joufi (Biodegradation, 2026)

Elevated interleukin-36γ and gene polymorphisms implicate novel risk in essential hypertension - Alishba Kainat; Fazlul Aziz Mian; Muhammad Asif Nawaz Khan; Mubeen Tabish Nasim; Syed Muhammad Nurulain; Nazia Bibi; Syed Tahir Abbas Shah; Muhammad Jadoon Khan; Sabir Hussain (Immunogenetics, 2026)

Modeling groundwater dynamics in a low-lying sedimentary island driven by recharge variability, climate change, and water demand - Muhammad Qasim Mahmood; Xiuquan Wang; Farhan Aziz; Qing Li; Nadeem Tariq (Journal of Hydrology, 2026)

Assessment of Fine Particulate Matter (PM2.5) Induced Cyto-Genotoxicity in a Highly Polluted Urban Environment: Evidence from Lahore, Pakistan - Meerub Shazad; Muhammad Muddassir Ali; Syed Aziz ur Rehman; Maryam Javed; Jabir Hussain Syed; Asad Ullah (Water, Air, & Soil Pollution, 2026)

Correction: Molecular characterization and green synthesis of iron oxide nanoparticles from Ureibacillus chungkukjangi for methylene blue degradation - Muhammad Naveed; Muhammad Asim; Tariq Aziz; Shumaila Ibrahim; Maida Salah Ud Din; Maryam M. Alomran; Ashwag Shami; Fakhria A. Al-Joufi; Ahmad A. Alghamdi; Abdullah A. Alqasem; Ahmed M. Basri; Majid Alhomrani (Antonie van Leeuwenhoek, 2026)

Immunopharmacological and structural design of a polyprotein based multi epitope vaccine against Powassan virus - Aasia Kalsoom; Syed Hussain Abidi; Sohail Ameer Marwat; Ghulam Shabbir; Muhammad Naveed; Aiman Muhammad Ashraf Mughal; Muhammad Nouman Majeed; Shereen Magdy Korany; Basma Magdy Korany; Khaled Alzhrani; Tariq Aziz (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Biomass-derived biochar as a precursor for graphene-like carbon materials via slow pyrolysis: A review - Illa Rizianiza; Eny Kusrini; Ahmad Indra Siswantara; Muhammad Aziz; Ponky Ivo; Imam Jauhari Maknun; Rendika Rumaldin Ichsan; Kuntum Khoiro Ummatin; Anwar Usman (Journal of Environmental Chemical Engineering, 2026)

Impact of Various Global Digital Elevation and Crustal Density Models on Accurate Topographic Correction for Geoid Modelling Over East Malaysia - Noorhurul Ain Othman; Muhammad Faiz Pa’suya; Ami Hassan Md Din; Ramazan Alpay Abbak; Mohamad Azril Che Aziz; Chivatsi Jonathan Nyoka; Nurul Shafiqah Hazelin Noor Azmin; Afreena Nisha Mohd Zamri (Pure and Applied Geophysics, 2026)

Seroprevalence of crimean-congo hemorrhagic fever virus in large wildlife: a systematic review and meta-analysis - Aziz Ul-Rahman; Muhammad Abu Bakr Shabbir; Muhammad Zubair Shabbir; Muhammad Asif Raza (European Journal of Wildlife Research, 2026)

Carbon finance: global trends and future research directions - Sidra Zahid; Shahab Aziz; Muhammad Rizwan Nazir; Muhammad Imran Nazir; Sidra Gazali (Environment, Development and Sustainability, 2026)

The Influence of Policy Indicators on Circular Economy Metrics in Australia: Application of Asymmetric Analysis - Suleman Sarwar; Afifa Qadeer; Rida Waheed; Ghazala Aziz; Muhammad Wasim Hussan (Circular Economy and Sustainability, 2026)

Integrative 16S rRNA characterization, pan-genome, and immunoinformatics approaches for the design of a multi-epitope vaccine against Bacillus cereus, a foodborne pathogen - Muhammad Asim; Muhammad Naveed; Tariq Aziz; Muhammad Toheed; Hafiz Muzzammel Rehman; Nawal Al-Hoshani; Rania Ali El Hadi Mohamed; Maher S. Alwethaynani; Areej A Alhhazmi; Manal F. Elkhadragy (World Journal of Microbiology and Biotechnology, 2026)

Lead and cadmium contamination in soils: impacts and phytoremediation strategies using ornamental plants, nanoparticles, and organic growth regulators - Sumbal Ammara; Muhammad Tariq Rafiq; Basharat Ali; Rukhsanda Aziz; Maria Aziz (Environmental Monitoring and Assessment, 2026)

Fe-MIL-101/Ti3C2Tx heterostructures via In-Situ solvothermal strategy for efficient oxygen evolution reaction - Shumaila Bibi; Muhmmad Irfan; Faiza Jan Iftikhar; Inas A. Ahmed; Muhammad Zahid Qureshi; Ahsan Sharif; Shu-Juan Bao; Aziz ur Rehman (Fuel, 2026)

Appraisal and Optimization of Electrocoagulation Performance for Battery Industry Wastewater Treatment via Response Surface Methodology - Aziz Ur Rahman; Muhammad Hashim Zubari; Azizuddin Shaikh (Water, Air, & Soil Pollution, 2026)

Unveiling Pakistan’s hydro-climatic shifts: trends and change-points in soil moisture and potential evapotranspiration across Pakistan’s climatic zones - Darakshan Naeem; Abdullah Taib; Muhammad Awais; Rizwan Aziz; Muhammad Zaman (Meteorology and Atmospheric Physics, 2026)

Nitrogen fertilization shapes rhizosphere microbiome to boost peanut yield: A two-year field study - Xiangjun Kong; Peipei Jia; Lijie Li; Ali Muhammad; Rui Wang; Aziz Khan; Jaya Nepal; Fei Li; Zhiyong Zhang (Applied Soil Ecology, 2026)

Statistical optimization of exopolysaccharides by indigenously isolated Lactobacillus strain under submerged fermentation - Madah Zahra Awan; Fouzia Tabssum; Muhammad Nadeem; Najeeb Ullah; Abid Sarwar; Neha Mazhar; Tariq Aziz; Ashwag Shami; Hanan Abdulrahman Sagini; Saleh A. Alsanie; Nouf Abdullah Alharbi; Mansour Albalji (World Journal of Microbiology and Biotechnology, 2026)

Assessment of urban and peri-urban grazing practices from herders and local community perspective in the semiarid region of Pakistan - Muhammad Farooq Azhar; Ghulam Yasin; Asghar Ali; Abida Aziz; Ghulam Yasin; Daniyal Hussain; Ehsan Ali (Environmental Monitoring and Assessment, 2026)

Synergistic effects of zinc and reduced glutathione application on growth, yield, gas exchange attributes, water relations, and metabolite profiles in Zea mays (L.) plants under water deficit irrigation - Farah Saeed; Qasim Ali; Suliman Mohammed Suliman Alghanem; Abida Kausar; Rashida Perveen; Haifa Abdul Aziz Sakit Alhaithloul; Muhammad Rizwan (South African Journal of Botany, 2026)

Individual and combined decontamination effect of aqueous ozone and plant extracts on fungi and aflatoxins in brown rice - Iqra Naeem; Amir Ismail; Yun Yun Gong; Muhammad Riaz; Muhammad Arif Shahzad; Aneela Hameed; Mubashir Aziz; Asif Mahmood; Waheed Al Masry; Muhammad Latif; Sher Ali; Carlos A.F. Oliveira (Food Control, 2026)

Synergistic photo-assisted AOPs using acid-modified biochar: Enhanced micropollutant levofloxacin degradation in industrial wastewater - Muhammad Irtaza Sajjad Haider; Guijian Liu; Balal Yousaf; Muhammad Arif; Kiran Aziz; Bisma Sattar; Muhammad Zeeshan Gulzar; Hameer Chand; Ruijia Liu (Desalination, 2026)

Bacterial Metabolite-Derived NDM-1 Inhibitors: A Computational Strategy to Overcome β-Lactam Resistance - Bader S. Alotaibi; Farhat Shabbir; Muhammad Umer Khan; Iqra Ahmad; Hira Khalid; Shahid Aziz; Abid Ali; Sonia Younas; Hanna Dib; Khaled Fahmi Fawy; Umar Nishan; Mohibullah Shah (Probiotics and Antimicrobial Proteins, 2026)

Chaotic transitions and multistable regimes in a nonlinear wave model through hybrid analytical–numerical techniques - Muhammad Iqbal; Syeda Sarwat Kazmi; Muhammad Bilal Riaz; Muhammad Aziz Rehman (Modeling Earth Systems and Environment, 2026)
The modified Zakharov–Kuznetsov (mZK) model is a fundamental framework for describing nonlinear phenomena in plasma oscillations, optical systems, discrete electrical lattices, and oceanic wave dynamics. In this work, we establish a unified framework that combines exact solution construction with dynamical systems analysis of the mZK equation. Using the modified Khater method and the Sardar subequation technique under a traveling wave transformation, we derive new and more general families of solitary traveling wave solutions, including trigonometric, hyperbolic, rational, exponential–rational, and complex soliton forms. We show how free parameters govern the existence, shape, and stability of these solutions, with two- and three-dimensional MATLAB simulations illustrating their structures. Furthermore, we reformulate the mZK equation as a planar dynamical system and classify its qualitative features through phase portraits, identifying centers, saddles, and cusps. With the inclusion of periodic external forcing, the reduced system displays bifurcation and chaos, following a period-doubling route with multistability and sensitivity to parameter variations. To the best of our knowledge, this is the first study that simultaneously delivers exact soliton solutions and a complete nonlinear dynamics characterization of the mZK equation. This integrated approach provides a novel template for investigating broader classes of nonlinear evolution equations.

GC-MS Profiling, Cytotoxicity and Antiviral Activity of Caulerpa lentillifera and C. macrodisca from Northern Coastal Waters of Borneo Island, Eastern Malaysia - Mohammad Tamrin Mohamad Lal; Elden Sai Long Chang; Zy Chee Wong; Leong Seng Lim; Muhammad Dawood Shah; Wahidatul Husna Zuldin; Gilbert Ringgit; Nur Azreen Arbi; Ahmad Hazim Abdul Aziz; Abdul Aziz Jaziri; Asep Awaludin Prihanto; Attabik Mukhamad Amrillah; et al. (Marine Biotechnology, 2026)

Exploring the biocatalytic potential of Amycolatopsis japonica DyP in degrading plasticizer and phenolic-derived xenobiotic compounds - Muhammad Naveed; Ayesha Saleem; Tariq Aziz; Sadia Jabeen; Sana Miraj Khan; Maida Salah Ud Din; Nantenaina Tombozara; Mayasar I. Al-zaban; Ashwag Shami; Hayam A. Alwabsi (Biodegradation, 2026)

Silver nanoparticles in water disinfection: a comprehensive overview on their mechanisms, benefits, and limitations - Muhammad Shehroz Zafar; Sana Ejaz; Farhan Ahmad; Ahmad H. Ibrahim; Sawsan S. Al-Rawi; Faiza Manzoor; Sadia Aziz; Saima Iqbal; Muhammad Adnan Iqbal (Archives of Microbiology, 2026)

Retraction Note: Toxic Effects of Titanium Dioxide Nanoparticles and Titanium Dioxide Bulk Salt in the Liver and Blood of Male Sprague-Dawley Rats Assessed by Different Assays - Muhammad Shakeel; Farhat Jabeen; Naureen Aziz Qureshi; Muhammad Fakhr-e-Alam (Biological Trace Element Research, 2026)

Green photocatalytic degradation of methylene green dye using oxalic acid and its metal complexes: Mechanistic and predictive insights from ANN, RSM, and DFT studies - Mohammad Tauseef Haider; Rizwan Ashraf; Talib H. Mawat; Faisal Jamil; Adnan Majeed; Anam Shahzadi; Faisal Qaleel; Haris Nadeem; Sabha Khalid; Asma Rehman; Sadia Aziz; Maryam Khalid; et al. (Journal of Water Process Engineering, 2026)

Biosynthesis and Biological Assessment of TiO₂ Nanoparticles from Pittosporum Tobira for Antioxidant, Anti-Inflammatory, Anti-Hemolytic Potential, and Polychlorinated Biphenyls Degradation - Muhammad Naveed; Muhammad Asim; Tariq Aziz; Saman Nasir; Maida Salah Ud Din; Nawal Al-Hoshani; Maher S. Alwethaynani; Maymounah A. Alrayyani; Fakhria A. Al-Joufi (Water, Air, & Soil Pollution, 2026)

Biochar and Montmorillonite in Combination Improved the Plant growth, physiology, Yield and Decreased Lead (Pb) Uptake in Wheat (Triticum aestivum L.) Under Pb Stress - Zaffar Malik; Suliman Mohammed Suliman Alghanem; Nasir Masood; Hina Rizvi; Muhammad Waseem; Ahmad Ali; Haifa Abdul Aziz Sakit Alhaithloul; Muhammad Rizwan (Journal of Soil Science and Plant Nutrition, 2026)

Heavy Metals Bioaccumulation in Riparian Vegetation: A Multi-Species Biomonitoring Framework Using Total X-Ray Reflection Fluorescence Spectroscopy - Shakeel Ahmed Talpur; Simonetta Cristina Di Simone; Aziz Ahmed; Hafeez Ahmed Talpur; Muhammad Yousuf Jat Baloch; Francesco Stoppa; Luigi Menghini; Beatrice Maria Sole Giambastiani; Gianluigi Rosatelli (Environmental Processes, 2026)
Heavy metal contamination in Mediterranean riparian ecosystems presents serious risks to biodiversity and human health, requiring innovative biomonitoring methods for polluted watersheds. This study developed a comprehensive biomonitoring framework for an industrially impacted Mediterranean river basin, with approximately 100,000 tons of contaminated waste in landfills from decades of metallurgical processing. We investigated heavy metal bioaccumulation patterns in five taxonomically diverse native riparian species ( Equisetum arvense , Laurus nobilis , Rubus ulmifolius , Sambucus nigra , and Salix alba ) across contaminated and reference sites using Total Reflection X-ray Fluorescence (TXRF) spectroscopy. TXRF was validated against Inductively Coupled Plasma Atomic Optical Spectroscopy (ICP-AOS) using standard reference materials, demonstrating superior sensitivity for trace element detection in plant matrices. Heavy metal concentrations varied significantly among species and sites in riparian vegetation, with Fe (23.14 ± 5.21 mg/kg), Mn (2.74 ± 0.89 mg/kg), and Cr (3.33 ± 1.12 mg/kg) showing the highest accumulation. Laurus nobilis appeared as a multi-metal hyperaccumulator with the highest Pollution Load Index (PLI = 2.67) and exceptional accumulation of Cr (14.74 mg/kg) and Fe (63.64 mg/kg). Statistical analysis (Kruskal-Wallis test, p < 0.05) confirmed that Mn and Cr represented primary anthropogenic pollutants, with contaminated sites showing 2.20-fold and 1.92-fold increases, respectively. Principal Component Analysis revealed distinct co-accumulation networks, with Fe-Cr-Ni-Cu forming synchronized uptake mechanisms, while Mn operated independently. Biogeochemical ratio analyses (Fe/Zn, Cu/Mn) provided sensitive contamination indicators, detecting physiological stress beyond simple concentration measurements. Results support species-specific phytoremediation strategies aligned with UN Sustainable Development Goals, with Laurus suitable for multi-metal extraction and Equisetum for Mn-specific remediation, advancing sustainable environmental management in industrially impacted Mediterranean watersheds.

Plant-derived biostimulants: Emerging trends, breakthroughs and challenges in 2024 - Qurat Ul Ain Hyder; Abida Aziz; Muhammad Farooq Azhar; Muhammad Hasnain Haider; Nazim Hussain (Organic Agriculture, 2026)

Evaluation of leaf extracts of Moringa oleifera Lam. On testosterone enanthate-induced polycystic ovary syndrome (PCOS) in mice - Shakeela Khalid; Muhammad Arshad; Farzana Siddque; Muhammad Sajid Arshad; Marina Sajid; Waseem Khalid; Zaira Aziz; Muhammad Zubair Khalid; Sulaiman Ali Alharbi; Mohammad Javed Ansari; Abdellah Zinedine; Elena Bartkiene; et al. (Advances in Traditional Medicine, 2026)
Polycystic ovary syndrome (PCOS) is a multifactorial endocrinological and metabolic disorder that affects women of reproductive age. It is often associated with hyperandrogenism, obesity, anovulation, infertility and insulin resistance. In this study, the imminent efficacy of MoLP ( Moringa oleifera leaf powder) and MoLE ( M. oleifera leaf extract) in treating PCOS in female albino mice was explored. Female albino mice were injected with testosterone enanthate [1.0 mg/100 g body weight (b.w.)] for 35-days to induce PCOS. For the treatment, mice were administered with M. oleifera leaf powder (250 and 500 mg/kg b.w.), M. oleifera leaf extract (250 and 500 mg/kg b.w.), and metformin (250 mg/kg b.w.) for 14 days. Following the intervention, body weight, blood glucose, c-peptide, testosterone, follicle-stimulating hormone (FSH) and luteinizing hormone (LH) levels and stages of the estrus cycle were measured at 0, 7 and 14 days. The ovaries were examined stereologically to determine the number and diameter of follicles. Results indicated that MoLP, MoLE (500 mg/kg b.w.) and metformin (250 mg/kg b.w.) significantly decreased body weight, blood glucose, c-peptide, testosterone and LH levels while increasing FSH levels and ovary weight over time compared to PCOS-induced mice. Additionally, regulation of the estrus cycle and folliculogenesis in PCOS-induced mice was observed. Overall, the present study revealed that M. oleifera may have the potential as a therapeutic intervention for PCOS. Graphical Abstract

Health risk evaluation of toxic metals in food crops irrigated with wastewater of Hattar Industrial Estate, Pakistan: a simulated gastrointestinal model approach - Ummama Khan; Rukhsanda Aziz; Muhammad Arshad; Basharat Ali; Muhammad Suhaib; Muhammad Tariq Rafiq (Environmental Monitoring and Assessment, 2026)

Fermentation-based valorization of agro-industrial cereal wastes and by-products - Muhammad Zeeshan Adil; Sebahat Oztekin; Afifa Aziz; Deniz Gunal-Koroglu; Esra Capanoglu; Andres Moreno; Waseem Khalid; Tuba Esatbeyoglu (Trends in Food Science & Technology, 2026)

Walk, swim and paddle: Qualitative research reframing children's independent mobility through capability and rhythmanalysis - Janatun Naim Yusof; Suzanna Noor Azmy; Noradila Rusli; Muhamad Solehin Fitry Rosley; Nadzirah Hosen; Tengku Intan Suraya Tengku Aziz; Muhammad Farid Azizul Azizui (Journal of Transport Geography, 2026)

A modelling approach for Mangrove carbon dynamics using integrated optical and SAR data in Balikpapan Bay, Indonesia: algorithm development and accuracy enhancement - A. A. Md. Ananda Putra Suardana; Nanin Anggraini; Muhammad Rizki Nandika; Devica Natalia Br Ginting; Nugraheni Setyaningrum; M. Amar Sajali; Azura Ulfa; Kholifatul Aziz; Kuncoro Teguh Setiawan; Ratih Dewanti Dimyati (Modeling Earth Systems and Environment, 2026)

The influence of community perceptions and practices on the sustainability of Pulau Kapas Marine Park - Muhammad Naqib Hasri; Nazli Aziz; Nurul Huda Sapehee; Nur Qamarina Mohmad Fuad; Ahmad Irsyad Ahmad; Tengku Balkis Tunku Shahar Tengku Abdul Rashid; Nurashiqin Sallih Udin; Abdul Rahman Abdul Latip (Journal of Coastal Conservation, 2026)

Ethnoecology of the Wakhi community in Broghil Valley, Chitral, Pakistan - Hasin Sahar; Lal Badshah; Muhammad Abdul Aziz; Allah Ditta (Genetic Resources and Crop Evolution, 2026)

Molecular identification of the blaOXA gene in Bacillus cereus and AI-driven optimization of natural phytochemicals for foodborne illness treatment - Muhammad Naveed; Muhammad Asim; Tariq Aziz; Maida Salah Ud Din; Muhammad Nouman Majeed; Ammena Y. Binsaleh; Nawal Al-Hoshani; Maher S. Alwethaynani; Abeer M. Alghamdi; Fakhria A. Al-Joufi (Antonie van Leeuwenhoek, 2026)

Marine Drug Design for Epitheliocytis Rendering AI ‐Assisted Bioisosteric Replacement of Salicin - Muhammad Naveed; Khushbakht Javed; Tariq Aziz; Rahmana Wazir; Imran Ali; Ayaz Ali Khan; Ashwag Shami; Maher S. Alwethaynani; Fahad Al‐Asmari; Fakhria A. Al‐Joufi (Journal of Fish Diseases, 2026)
Epitheliocystis is a distinctive and relatively understudied bacterial infection of finfish skin and gill epithelia that occurs intracellularly and results in the enlargement of the host cells. The Candidatus Syngnamydia salmonis is a bacterial pathogen that affects fish, especially salmon species like trout and salmon. The production of Epitheliocystis by Candidatus Syngnamydia salmonis poses several challenges to the aquaculture industry. Currently, limited drugs and therapies are available to effectively manage and cease the spread of this disease. The goal of this study was to develop a potential drug target for the treatment of epitheliocystis. Salicin, an organic glucoside widely known for its anti‐inflammatory characteristics, was chosen as the initial compound because of its pharmacological significance and confirmed as a bioisostere (a compound with identical biological activities but a different structure). The Xundrug MolOpt AI generative model of bioisosteric replacement tool was chosen as the optimisation technique in a cognitive exertion to improve the novel drug candidate salicin by its AI‐assisted bioisosteric replacement. To retrieve the docking results, the top three ligands from Xundrug and the cell division protein of Candidatus Syngnamydia salmonis were uploaded to the HDOCK web server, which utilises a hybrid docking technique combining template‐based modelling for docking. The target drug candidate was selected based on model 17's highest docking score of 135.6 kcal/mol. Furthermore, the Lipinski rule of five and the ADMET properties of the Bioisosteric Replaced Salicin model 17 (BRS‐17) were carefully explored. The results showed that BRS‐17 fulfilled the pharmacophore characteristics criteria, hence making it an ideal target candidate for Candidatus Syngnamydia salmonis' cell division protein. Additionally, the results are supported by −6.735Kcal/mol docking score predicted by DockThor. With the help of the supporting information from this study, the proposed drug design can close the gap in earlier studies for resistance to antibiotic treatments. It is suggested that in vitro tests be performed on this drug to show the effectiveness of the suggested design.

Carboxymethyl cellulose: Structural modifications and their impact on barrier and mechanical properties for sustainable food packaging - Batool Esmat; Shumaila Bibi; Mohamed Mohamed Soliman; Hamdy Khamees Thabet; Muhammad Ahmad Wattoo; Muhammad Altaf Nazir; Zeinhom M. El-Bahy; Aziz ur Rehman (Journal of Stored Products Research, 2026)

Exploring microbiological transformation of glutamate to γ-aminobutyric acid unleashed by a potential Lactobacillus spp. isolated from commercial cheese samples - Sikander Ali; Taha Shafi; Iram Liaqat; Muhammad Usman Ahmad; Ifrah Shabbir; Tariq Aziz; Maha Alharbi; Ashwag Shami; Fahad Al-Asmari; Ibrahim Faisal Halawani; Abdullah A. Alqasem; Reham M. Mashat; et al. (International Dairy Journal, 2026)

Emerging contaminants and their influence on plants: An in-depth review - Sadia Aziz; Sania Zaib; Azhar Iqbal; Muhammad Asif Chuadhry; Shaheen Shahzad; Bikram Dhara; Athanasios Alexiou; Partha Biswas; Mohamed M. Abdel-Daim; Shabana Bibi (Environmental Toxicology and Pharmacology, 2026)

Functionalization of Mn2+ with Zr-MOF for ratiometric fluorescent and smartphone-integrated colorimetric detection of hydrogen peroxide - Xiaojing Chai; Ruirui Zhao; Muhammad Asif; Ayesha Aziz; Chuan Dong; Youhong Tang; Shaomin Shuang; Yujing Guo (Chemical Engineering Journal, 2026)

Numerical simulations of a heavy rainfall event in the Sahelian region of Zinder in Niger - Abdoul Aziz Saidou Chaibou; Kodjo Gboneh Gratien Edoh; Soliou Kègnidé Adéchinan Gbadamassi; Marisol Obono Ndong Abogo; Inoussa Abdou Saley; Isaac Kwesi Nooni; Ibrah Seidou Sanda; Moussa Mounkaila Saley; Muhammad Ilyas Abro; Boubacar Moumouni Kaougé; Ousmane Baoua; Gaptia Lawan Katiellou; et al. (Atmospheric Research, 2026)

Adaptability of Barbados Blackbelly rams towards elevated temperature-humidity index assessed through reproductive physiology and behaviour - Muhammad Syafiq Roslan; Mohd Shahmi Hakimi Mazlishah; Noorhidayah Mamat; Nor Azlina Abd Aziz; Noor Hashida Hashim; Nuradilla Mohamad-Fauzi (Small Ruminant Research, 2025)

Leveraging green roof technology: Stakeholder analysis of sustainable urban landscape in the developing regions of South Asia - Mehak Shehzad; Adnan Younis; Sabir Aziz; Muhammad Khizar; Noor ul Ain; Muhammad Asad Shabbir (Land Use Policy, 2025)

Alleviating stocking density stress in juvenile rainbow trout (Oncorhynchus mykiss) through dietary nano-selenium: Effects on growth, antioxidant activity, and immune response - Mashooq Ali; Aqsa Akram; Farid Ahmad Jan; Aziz Ahmad; Ashiq Hussain; Fahim Ullah Khan; Muhammad Arshad (Journal of Trace Elements in Medicine and Biology, 2025)

DFT insights into the adsorption mechanisms of environmental gases on 2H-WTe₂ for potential sensing applications - Saleh S. Alarfaji; Niaz Ahmad; Swera Khalid; Farooq Aziz; Tahir iqbal; Muhammad Isa Khan (Journal of Environmental Chemical Engineering, 2025)

Transformation of wet chemically derived ZnGa-LDH to ZnO:GaN nano-alloys for PMS activated wastewater remediation - Yasir Abbas; Kanwal Shabbir; Haider Aziz; Ijaz Hussain; Hafiz M. Adeel Sharif; Muhammad Ahsan Iqbal; Majid Basharat; Haoliang Wang; Niaz Ali Khan (Journal of Environmental Chemical Engineering, 2025)

Retraction notice to “Investigation on synthesis of ternary g-C3N4/ZnO–W/M nanocomposites integrated heterojunction II as efficient photocatalyst for environmental applications” [Environ. Res. Volume 217, 15 January 2023, 114621] - Misbah Malik; Thomas Len; Rafael Luque; Sameh M. Osman; Emilia Paone; Muhammad Imran Khan; Muhammad Ahmad Wattoo; Muhammad Jamshaid; Aqsa Anum; Aziz ur Rehman (Environmental Research, 2025)

Thiourea-modified silk cotton carbon as an efficient sulfur host: A green approach for advanced aluminum-sulfur battery - Muhammad Faheem; Arshad Hussain; Ananda Sholeh Rifky Hakim; Muhammad Ali; Abbas Saeed Hakeem; Md. Abdul Aziz (Biomass and Bioenergy, 2025)

Impact of Tannery Effluents on Groundwater Quality and Human Health in Kasur, Pakistan - Mohammad Salman Faisal; Muhammad Awais; Rohina Bashir; Muhammad Bilal Shakoor; Rizwan Aziz; Muhammad Rizwan; Affaq Ali; Simal Akhtar; Noor Fatima (Water, Air, & Soil Pollution, 2025)

The effects of nanocurcumin on immune-related factors in the ankylosing spondylitis patients: a double-blind, randomized, placebo‐controlled clinical trial - Halmat M. Jaafar; Dana Muhammad Hamad Ameen; Talar Ahmad Merza Mohammad; Aziz Muzafar Jafaar (Molecular Biology Reports, 2025)

Dynamical transitions and multistability in nonlinear wave systems: dual analytical insights into the geophysical Korteweg–de Vries Equation - Muhammad Iqbal; Muhammad Bilal Riaz; Muhammad Aziz ur Rehman; Mohie M. Alqezweeni (Modeling Earth Systems and Environment, 2025)

Effect of Different Application Rates and Types of Biochar on Soil Biochemical Characteristics and Greenhouse Gas Emissions - Muhammad Abdullah Aziz; Mosaed A. Majrashi (Journal of Soil Science and Plant Nutrition, 2025)

Whole-Genome analysis of Bacillus subtilis MBBL2 genomic characterization and comparative genomics - Hajra Sohail; Muhammad Naveed; Tariq Aziz; Rania Ali El Hadi Mohamed; Fakhria A. Al-Joufi (Functional & Integrative Genomics, 2025)

Utilization of physicochemical approach to propose a strategy for biofilm inhibition - Ajab Khan; Muhammad Aasim; Noor Shad Bibi; Haris Saddique; Hizb Ullah; Zohaib Khan; Umar Aziz; Nadir Zaman Khan; Waqar Ali; Noor Muhammad (Biofouling, 2025)

Monitoring and optimization of heavy metal phytoextraction in constructed wetlands amended with organic chelators - Mujahid Farid; Ambreen Mussarat; Muhammad Zubair; Zaki ul Zaman Asam; Ayesha Siddiqua; Wajiha Sarfraz; Roha Murtaza; Suliman Mohammed Suliman Alghanem; Haifa Abdul Aziz Sakit Alhaithloul (Environmental Monitoring and Assessment, 2025)

Aspergillus spp and aflatoxins in Pakistani rice: A case study on the decontamination effect of accelerated aging and improved storage practices - Iqra Naeem; Amir Ismail; Yun Yun Gong; Muhammad Riaz; Aneela Hameed; Mubashir Aziz; Asif Mahmood; Waheed Al Masry; Muhammad Latif; Sher Ali; Carlos Augusto Fernandes de Oliveira (Toxicon, 2025)

Technical assessment for enhancing environmental sustainability of metallurgical exhaust gases to methanol process via electrochemical energy conversion - Po-Chih Kuo; Faruk Özdemir; Yin-Ping Wu; Biju Illathukandy; Wei Wu; Muhammad Aziz (Journal of Cleaner Production, 2025)

Effect of high-ratio co-firing of Samanea saman wood with low-rank coal on slagging, fouling, and ash-related problems in a drop tube furnace - Suyatno Suyatno; Hafizh Ghazidin; Ade Sana Ruhiyat; Fairuz Milkiy Kuswa; Feri Karuana; Prabowo Prabowo; Arif Darmawan; Kusdi Prijono; Tata Sutardi; Kusmiyati Kusmiyati; Achmad Nurfanani; Hanggi Eko Samudra; et al. (Biomass and Bioenergy, 2025)

Nonstationarity impacts on the assessment of drought conditions across diverse climate zones of Pakistan - Maryam; Rizwan Aziz; Ismail Yucel; Mahnoosh Moghaddasi; Muhammad Awais (Theoretical and Applied Climatology, 2025)

Metabolite characterization of probiotic Enterococcus Faecium for targeting Salmonella Entrica gut bacteria causing gastroenteritis - Kashef Choudhary; Muhammad Naveed; Tariq Aziz; Syeda Izma Makhdoom; Muhammad Waseem; Nada K. Alharbi; Fatma Alshehri; Ashwag Shami; Maher S. Alwethaynani; Fahad Al-Asmari; Areej A. Alhhazmi; Fakhria A. Al-Joufi (Antonie van Leeuwenhoek, 2025)

Artificial neural network optimized green synthesis of cysteine-conjugated silver nanoparticles for antibacterial activity against staphylococcus nepalensis to combat cystitis - Muhammad Asim; Muhammad Naveed; Tariq Aziz; Maida Salah Ud Din; Fatma Alshehri; Ashwag Shami; Maher S. Alwethaynani; Deema Fallatah; Abeer M. Alghamdi; Fakhria A. Al-Joufi (Antonie van Leeuwenhoek, 2025)

Scalable biochar production from oil palm fronds and waste cooking oil: Techno-economic and policy-oriented evaluation for rural deployment - Indra Purnama; Anisa Mutamima; Sunarno Sunarno; Imran Al Ucok Nasution; Eka Syaputra; Muhammad Aziz (Journal of Cleaner Production, 2025)

Recent strategy on green synthesis of mesoporous silica from waste for a sustainable and circular economy - Reva Edra Nugraha; Nur Aini Fauziyah; Silvana Dwi Nurherdiana; A.R. Yelvia Sunarti; Abdul Aziz; Ni Ketut Sari; Ajit K. Sarmah; Muhammad Al Muttaqii; Zuhriah Mumtazah; Novia Amalia Sholeha; Hasliza Bahruji; Aishah Abdul Jalil; et al. (Journal of Environmental Chemical Engineering, 2025)

Sustainable and dual-optimized electrode design from waste resources for high-energy lithium–sulfur batteries - Mohsen Hajian Foroushani; Samane Maroufi; Rasoul Khayyam Nekouei; Muhammad Aziz; Veena Sahajwalla (Journal of Environmental Chemical Engineering, 2025)

Hybrid modeling of deep neural networks and unsupervised machine learning algorithms for missing well log prediction based on geological lithofacies similarities - Wakeel Hussain; Miao Luo; Muhammad Ali; Izhar Sadiq; Erasto E. Kasala; Tariq Aziz; Zuriyat Batool (Journal of Applied Geophysics, 2025)

Lignocellulosic biomass as a renewable resource: Driving second-generation biofuel innovation from agricultural waste - Irum Bukhari; Fazal Haq; Mehwish Kiran; Tariq Aziz; Sahid Mehmood; Muhammad Haroon (Biomass and Bioenergy, 2025)

Recent advances in layered double hydroixdes@MXene (LDHs@MXene) composites: Synthesis, properties, and catalytic applications - Sundas Riaz; Sami Ullah; Sanam Bashir; Aziz ur Rehman; Rashid Iqbal; Tayyaba Najam; Mostafa A. Ismail; Md Rezaul Karim; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Applied Clay Science, 2025)

Molecular characterization and green synthesis of iron oxide nanoparticles from Ureibacillus chungkukjangi for methylene blue degradation - Muhammad Naveed; Muhammad Asim; Tariq Aziz; Shumaila Ibrahim; Maida Salah Ud Din; Maryam M. Alomran; Ashwag Shami; Fakhria A. Al-Joufi; Ahmad A. Alghamdi; Abdullah A. Alqasem; Ahmed M. Basri; Majid Alhomrani (Antonie van Leeuwenhoek, 2025)

Molecular Simulation and Expression Analysis of Vitamin C and Curcumin in Mitigating Buprofezin-induced Genotoxicity and Inflammatory Responses in Balb/c Mice - Haleema Sadia; Irfan Zia Qureshi; Muhammad Naveed; Tariq Aziz; Manal F. Elkhadragy; Maher S. Alwethaynani; Fahad Al-Asmari; Areej A Alhhazmi; Hanan Abdulrahman Sagini; Suad Hamdan Almasoudi; Fakhria A. Al-Joufi (Cell Biochemistry and Biophysics, 2025)

Facile construction of chitosan-ternary metal selenide biopolymer-based composite for photocatalytic degradation of petroleum derive sunset yellow and acid black azo-dyes using response surface methodology RSM - Tariq Aziz; Muhammad Farhan; Adnan Khan; Nisar Ali; Javeed Azam; Sumeet Malik; Sarmad Ali; Nauman Ali; Hamayun Khan; Rayya Ahmed Al Balushi; Mohammad M. Al-Hinaai; Thuraya Al-Harthy (Environmental Science and Pollution Research, 2025)

Dispersion stability of a water-based ternary hybrid nanofluid with Al2O3, CuO, and graphite: an experimental and RSM modeling approach - Md. Ramim-Ul Hasan; Tanjimur Rashid; Md. Emdadul Hoque; Muhammad Aziz; Md. Sanowar Hossain (Next Research, 2025)

Effects of replacement of soybean meal with fermented soybean meal on growth performance, nutrient digestibility and carcass characteristics in broiler - Ali Husnain; Urooj Anwar; Asfa Fatima; Riaz Mustafa; Umar Farooq; Waseem Abbas; Muhammad Farooq Khalid; Muhammad Ashraf; Muhammad Aziz ur Rahman (Livestock Science, 2025)

Isolation, Identification, biochemical and molecular characterization of potential source of enterotoxigenic strains of Staphylococcus aureus from the bovine raw and mastitis milk - Sikander Ali; Farzana Nazir; Muhammad Usman Ahmad; Hira Sarfraz; Abid Sarwar; Tariq Aziz; Ashwag Shami; Fahad Al-Asmari; Areej A. Alhhazmi; Abeer M. Alghamdi; Fakhria A. Al-Joufi (International Dairy Journal, 2025)

Bamboo charcoal mitigates oxidised LDL-induced foam cell formation via molecular interaction and adsorption: Evidence from in silico and in vitro studies - Mutaman Hussein Abdullah; Ahmad Naqib Shuid; Mohd Yusmaidie Aziz; Muhammad Azrul Zabidi; Muhammad Mahyiddin Ramli; Rafeezul Mohamed (Chemistry and Physics of Lipids, 2025)

Optimized liquid hydrocarbon production via co-pyrolysis of Nypa fronds and polypropylene using fly ash catalyst - Padil Padil; Sunarno Sunarno; Anisa Mutamima; Indra Purnama; Nurfatihayati; Panca Setia Utama; Alhayat Raja Noor; Sunariyo Sunariyo; Muhammad Aziz (Bioresource Technology Reports, 2025)

Impact of Reconditioning Treatment at Different Temperatures on Potato Cultivars Stored Under Cold Conditions - Adnan Amjad; Aziz Mouhaddach; Hanane Latifi; Rabia Mehboob; Tusneem Kausar; Mohamed Bouhrim; Ramzi A. Mothana; Omar M. Noman; Farzana Siddique; Muhammad Bilal; Shehnshah Zafar; Ashiq Hussain (Potato Research, 2025)

Fracture analysis and reservoir potential of Jurassic-Paleocene rocks exposed in lower Orakzai area, Lesser Himalayas, Pakistan - Wasif Ullah; Syed Ali Turab; Muhammad Awais Aziz; Nasar Khan (Carbonates and Evaporites, 2025)

The green supply chain conundrum: exploring the interplay of practices, performance, and technology in shaping SME sustainability in developing country - Ikramuddin Junejo; Jan Muhammad Sohu; Aiza Aziz Qureshi; Saba Shaikh; Faisal Ejaz; Tahir Saeed Jagirani; Md Billal Hossain (Environment, Development and Sustainability, 2025)

Trends in extracting protein from microalgae Spirulina platensis , using innovative extraction techniques: mechanisms, potentials, and limitations - Samran Khalid; Kashmala Chaudhary; Humera Aziz; Sara Amin; Hassan Mehmood Sipra; Sadia Ansar; Husnain Rasheed; Muhammad Naeem; Helen Onyeaka (Critical Reviews in Food Science and Nutrition, 2025)

Effect of Different Levels of Copper Oxide (CuO) Nanoparticles and Biochar on Soil’s Microbial Activities and Maize (Zea Mays L.) Growth - Muhammad Abdullah Aziz; Sana Zahra; Bilal Adil; Amir Naserin; Muhammad Asad Hameed; Ijaz Ali; Temoor Ahmed; Ajaz Ahmad (Journal of Soil Science and Plant Nutrition, 2025)

Microplastic contamination in agricultural soils from mulch films and organic amendments: Transformation mechanism, soil-Biota toxicity, and future perspectives - Bisma Sattar; Guijian Liu; Balal Yousaf; Muhammad Arif; Muhammad Zeeshan Gulzar; Muhammad Irtaza Sajjad Haider; Rabia Safeer; Samra Ijaz; Muhammad Awais Haider; Kiran Aziz (Waste Management, 2025)

Life cycle greenhouse gas emission reduction potential of alternate wetting and drying in rice cultivation under Malaysian major granary areas - Nurul Ain Abu Bakar; Mohd Saufi Bastami; Muhammad Hariz Abdul Rahman; Rozimah Mohd Rasdi; Mohd Aziz Rashid; Shahida Hashim; Mohd Najib Mohd Yusof; Fauzi Jumat; Mohd Fairuz Md Suptian (Journal of Cleaner Production, 2025)

Integrated groundwater quality assessment using GIS and statistical analysis techniques at Islamkot subdistrict in the Thar desert area - Imran Aziz Tunio; Sheeraz Ahmed Memon; Love Kumar; Habibullah Abbasi; Habib Ursani; Sher Muhammad Ghoto (Groundwater for Sustainable Development, 2025)

Assessing human health risks associated with wastewater flooding - Farhan Aziz; Xiuquan Wang; Muhammad Qasim Mahmood; O’Keeffe Juliette (Environmental Impact Assessment Review, 2025)

Genotypic Profiling, Functional Analysis, Cholesterol-Lowering Ability, and Angiotensin I-Converting Enzyme (ACE) Inhibitory Activity of Probiotic Lactiplantibacillus plantarum K25 via Different Approaches - Tariq Aziz; Hu Hangyu; Muhammad Naveed; Muhammad Aqib Shabbir; Abid Sarwar; Jasra Nasbeeb; Yang Zhennai; Metab Alharbi (Probiotics and Antimicrobial Proteins, 2025)

Efficacy of Flumetsulam for Post-Emergence Weed Management in Chickpea (Cicer Arietinum L.) Under the Semi-Arid Region of Pakistan - Muhammad Khuram Razzaq; Ali Aziz; Faisal Hayat; Muhammad Zia Ul Haq; Irfan Rasool; Muhammad Naveed Babur; Ali Aslam; Sher Muhammad; Ammara Tahir; Khalid Hussain (Journal of Crop Health, 2025)

Revealing Lactiplantibacillus Plantarum K25 Derived (Z)-18-Octadec-9-Enolide in Modulating Aquaporin-8 in Colorectal Cancer by Bridging the Gut Microbiome and Membrane Biology - Tariq Aziz; Muhammad Aqib Shabbir; Abid Sarwar; Zhennai Yang; Lin Lin; Wafa Abdullah I. Al-Megrin; Ashwag Shami; Maher S. Alwethaynani; Areej A Alhhazmi; Fahad Al-Asmari; Fakhria A. Al-Joufi; Deema Fallatah (Cell Biochemistry and Biophysics, 2025)

An overview of ethnobotanical investigations for primary healthcare: a case study from Mardan district, Pakistan - Muhammad Mohsin; Musheerul Hassan; Ivana Vitasović-Kosić; Mona S. Alwahibi; Sher Wali; Qoryog’diyev Zufar Oxunjonovich; Muhammad Abdul Aziz; M. Ajmal Ali; Rainer W. Bussmann; Arshad Mehmood Abbasi (Plant Biosystems, 2025)

Retrofitting the natural gas combined cycle through integration with chemical looping hydrogen generation and ammonia synthesis toward a carbon-neutral trigeneration system - Azaria Haykal Ahmad; Alfian Muhammad Reza; Muhammad Aziz (Journal of Cleaner Production, 2025)

Urban flood modelling: Challenges and opportunities - A stakeholder-informed analysis - Muhammad Qasim Mahmood; Xiuquan Wang; Farhan Aziz; Nilay Dogulu (Environmental Modelling & Software, 2025)

Techno-economic assessment and life cycle analysis of restaurant food waste-to-electricity conversion in Malaysia and Singapore within a circular bioeconomy framework - Kai Chen Goh; Tonni Agustiono Kurniawan; Sulzakimin Mohamed; Dongdong Zhang; Muhammad Imran Khan; Mohd Hafiz Dzarfan Othman; Faissal Aziz; Abdelkader Anouzla; Choo Wou Onn (Biomass and Bioenergy, 2025)

Managing Fertilizer Rates and Tillage Depth to Improve Nitrogen Use Efficiency and Soil Health - Abdul Wakeel; Abdul Qadeer; Zunaira Bano; Muhammad Rizwan Shahid; Muhammad Rizwan; Aysha Kiran; Muhammad Sanaullah; Tariq Aziz; Robert Martin Rees; Arti Bhatia; Julia Drewer (Journal of Soil Science and Plant Nutrition, 2025)

Effect of Phosphorus Modified Cotton Stick Biochar on Growth, Photosynthesis, Enzymatic Activities and Lead (Pb) Uptake in Tomato Plants Grown in Pb-contaminated Soil - Zaffar Malik; Aleena Shabir; Ahmad Ali; Muhammad Naveed Aslam; Humera Aziz; Syed Farhan Haider Bukhari; Sana Noreen; Usama Ali Tahir; Muhammad Rizwan (Journal of Soil Science and Plant Nutrition, 2025)

Fluoride contamination in plum and peach orchards and its impact on earthworm growth and reproduction - Muhammad Nauman Ahmad; Shah Saud; Afia Zia; Muhammad Baseer Us Salam; Somaira Bibi; Ayaz AlI Khan; Tariq Aziz; Saleh A. Alghamdi; Abdulhakeem S. Alamri; Majid Alhomrani (Environmental Monitoring and Assessment, 2025)

CO2 capture using mixed amines: experimental DFT investigation with focus on improvements in cyclic efficiency and NO interference - Muhammad Haris; Arif Aziz; Muhammad Sohail; Waseem Sardar (Environmental Science and Pollution Research, 2025)

Effects of neem leaf extract on physiochemical traits and antioxidant activity of peach fruit during storage - Jianhui Li; Muhammad Hanif; Muhammad Azam; Muhammad Arslan Khan; Muhammad Ali Umer; Beenish Chaudhary; Imtiaz Hussain; Tariq Aziz Khan; Shoaib ur Rehman; Muhammad Awais; Riadh Ilahy; Hongru Liu; et al. (Journal of Stored Products Research, 2025)

A multi-dimensional approach to assess crop mapping and farmer strategies in drylands of Bamyan, Afghanistan - Arnaud Caiserman; Sayed Muhammad Baqer Hussaini; Aslam Qadamov; Roy C. Sidle; Aziz Ali Khan (Agricultural Systems, 2025)

Polycyclic aromatic hydrocarbons (PAHs) occurrences in water bodies, extraction techniques, detection methods, and standardized guidelines for PAHs in aqueous solutions - Rana Muhammad Mubeen Muhsin; Teh Sabariah Binti Abd Manan; Joseph Bidai; Muhammad Sarfraz Ahmad Mangat; Zarimah Mohd Hanafiah; Adel Gohari; Naveed Ahmad; Farooq Ahmad; Salmia Beddu; Nur Liyana Mohd Kamal; Daud Mohamad; Shatha Aser Hamad Aldala'in; et al. (Science of The Total Environment, 2025)

Experimental investigation of slagging and fouling in co-combustion of bituminous coal and sorghum waste: Insights into ash morphology and mineralogy - Moch. Zulfikar Eka Prayoga; Nesha Adelia; Adi Prismantoko; Romelan Romelan; Fairuz Milkiy Kuswa; Maharani Dewi Solikhah; Arif Darmawan; Zainal Arifin; Bambang Teguh Prasetyo; Muhammad Aziz; Prabowo Prabowo; Hariana Hariana (Fuel, 2025)

Investigating the dynamics of (3+1)-dimensional generalized nonlinear physical system via sensitivity and phase portraits - Muhammad Iqbal; Muhammad Bilal Riaz; Muhammad Aziz ur Rehman (Modeling Earth Systems and Environment, 2025)

Exploring chaos and stability: dynamic insights into the stochastic Davey-Stewartson system through advanced sensitivity analysis - Muhammad Moneeb Tariq; Muhammad Bilal Riaz; Tomas Kozubek; Muhammad Aziz-ur-Rehman (Modeling Earth Systems and Environment, 2025)
In this study, we investigate the stochastic Davey-Stewartson equation in the presence of noise. These two-dimensional integrable equations are higher-dimensional versions of the nonlinear Schrödinger equation. Davey-Stewartson equations are important in plasma physics, nonlinear optics, hydrodynamics, and other disciplines because the solutions they provide are valuable in understanding many complex physical phenomena. We employ a modified version of the $$\left( \frac{G'}{G^2} \right)$$ G ′ G 2 approach to handle variable-coefficient systems with imaginary components, such as nonlinear Schrödinger systems. We have discovered a wide range of precise traveling wave solutions, including solitons, kink, periodic, and rational solutions. These solutions may have a significant impact in the domains of engineering and plasma physics. The presented techniques effectively achieve a variety of exponential solutions, including bright, dark, single, rational, and periodic solitary wave solutions. We used MATLAB to simulate our findings and provide 3D, 2D, and counter graphs that illustrate the impact of noise on the precise solutions of the stochastic Davey-Stewartson problem. We apply the Galilean transformation to derive the planar dynamical system, which enhances our understanding of the system’s dynamical analysis. We also conduct a sensitivity analysis to observe the systematic response to various initial conditions. This analysis focuses on the symmetrical aspects of the system and includes the illustration of phase portraits with equilibrium points. We also investigate the chaotic behavior of the planer dynamical system by introducing an additional external force. We predict the system’s behavior to increase the value of intensity and frequency. Our analysis reveals periodic, quasi-periodic, and chaotic processes.

Assessment of Climate-resilient Cotton Genotypes Exhibiting High-temperature Tolerance - Sajid Ali; Waqas Shafqat Chattha; Aziz Ullah; Muhammad Zahid Ihsan; Waqar Shafqat; Abdel-Halim Ghazy; Muhammad Afzal; Bilal Ayub (Journal of Crop Health, 2025)

Active biomonitoring of stream ecosystems: untargeted metabolomic and proteomic responses and free radical scavenging activities in mussels - Muhammad Rivaldi; Andri Frediansyah; Solihatun Amidan Amatul Aziz; Andhika Puspito Nugroho (Ecotoxicology, 2025)

Exploring Green Practices: a Review of Carbon Dot-Based Sustainable Sensing Approaches - Kawan F. Kayani; Sewara J. Mohammed; Nian N. Mohammad; Mohammed K. Rahim; Muhammad S. Mustafa; Harez Rashid Ahmed; Wrya O. Karim; Mohammed K. Sidiq; Shujahadeen B. Aziz (Journal of Fluorescence, 2025)

Enhancing Efavirenz Bioavailability Via Polymer-Based Buccal Administration: Optimization and Characterization of Nanocrystal-Loaded Dissolving Microneedle Delivery Systems - Khairiyah Khairiyah; Muh. Bisfain Asaf; Nur Afni Annisa Achmad; Rachmatya W. Tuna; Irfan Kurniawan; Anugerah Yaumil Ramadhani Aziz; Maria Mir; Juan Domínguez-Robles; Mónica Millán-Jiménez; Ilyas Essadki-Aittaji; Ana B. Cobo-González; Muhammad Aswad; et al. (The AAPS Journal, 2025)

Socially responsible investment (SRI) a scientometric and bibliometric analysis and future research agenda (1991–2023) - Sidra Gazali; Shahab Aziz; Muhammad Imran Nazir (Environment, Development and Sustainability, 2025)

UBEM-SER: Role of sufficiency, efficiency and renewable in the decarbonization of commercial building stock at city scale - Usama Perwez; Muhammad Haseeb Rasool; Imran Aziz; Usman Zia (Sustainable Cities and Society, 2025)

Innovative circular bioeconomy and decarbonization approaches in palm oil waste management: A review - Kai Chen Goh; Tonni Agustiono Kurniawan; G. Abdulkareem AlSultan; Mohd Hafiz Dzarfan Othman; Abdelkader Anouzla; Faissal Aziz; Imran Ali; Joan Cecilia C. Casila; Muhammad Imran Khan; Dongdong Zhang; Choo Wou Onn; Ta Wee Seow; et al. (Process Safety and Environmental Protection, 2025)

Reinforcing urban resilience through sound landfill management: Addressing global climatic challenges with novel solutions - Kai Chen Goh; Tonni Agustiono Kurniawan; Mohd Hafiz Dzarfan Othman; Abdelkader Anouzla; Faissal Aziz; Imran Ali; Joan Cecilia C. Casila; Muhammad Imran Khan; Dongdong Zhang; Wei Dai; Choo Wou Onn; Ta Wee Seow (Process Safety and Environmental Protection, 2025)

Exergy destruction analysis of coal gasification with O2-H2O combined with chemical kinetics - Honghuan Wu; Xiangxiang Chen; Muhammad Aziz; Zuohua Huang; Yingjia Zhang (Fuel, 2025)

Supplementing high-fiber olive pomace and multi-enzymes to broiler chicken’s diet can improve health and performance - Osama Rahman Ghaffar; Dastan Mohammed Khoshnaw; Omer Rasool Ahmed; Sarwar Omer Aziz; Asrin Abdollahi; Nihayat Ibrahim Mohammed; Karzan Kareem Saleh; Niga Rzgar Ahmad; Mzhda Mohammed Majeed; Shiraz Ismail Muhammad; Srwsht Farhad Osman; Hawkar Azad Khdir (Tropical Animal Health and Production, 2025)

Scenario-based HEC-RAS 2D unsteady flow analysis of Shisper Lake for GLOF risk assessment - Junaid Aziz Khan; Muhammad Qamar Javed Pirzada; Muhammad Fahim Khokhar (Natural Hazards, 2025)

Physicochemical profiling and health risk evaluation of effluents from textile industries: insights from Faisalabad, Pakistan - Hina Sattar; Muhammad Anwar-ul-Haq; Humera Aziz; Umair Riaz; Ahmad Mahmood; Muhammad Rizwan; Munaza Naseem; Mona S. Alwahibi; Mohamed S. Elshikh; Muhammad Qasim; Rashid Iqbal (Toxicology and Environmental Health Sciences, 2025)

Effects of dietary organic selenium, vitamin C, and vitamin E supplementation on growth performance, serum biochemistry, and antioxidant status in juvenile Hypophthalmichthys molitrix - Hairui Yu; Maida Mushtaq; Saira Razzaq; Umar Ali; Muhammad Khan; Abdur Rahman; Guobo Quan; Mehroze Fatima; Saima Naveed; Muhammad Hammad Zafar; Muhammad Aziz ur Rahman (Frontiers in Marine Science, 2025)
The study aimed to evaluate the effects of dietary supplementation of selenium (Se), vitamin C, and vitamin E on growth performance, meat quality, and antioxidant status in Hypophthalmichthys molitrix juveniles. A total of 480 juveniles (mean weight: 20 ± 0.29 g) were randomly assigned to 24 aquaria (20 fish per 100 L), which were allocated to eight dietary treatments (three aquaria per treatment) following a completely randomized design. The dietary treatments included: (1) a basal diet without supplementation (Control), (2) selenium supplementation (S), (3) vitamin C supplementation (C), (4) vitamin E supplementation (E), (5) selenium and vitamin C supplementation (SC), (6) selenium and vitamin E supplementation (SE), (7) vitamin C and vitamin E supplementation (EC), and (8) selenium, vitamin C, and vitamin E supplementation (SCE). The supplementation levels were 0.9 mg/kg Se, 300 mg/kg vitamin C, and 100 mg/kg vitamin E, respectively. After a one-week acclimatization period, a 10-week growth trial was conducted. Fish fed the SCE diet exhibited significantly higher (p< 0.05) final weight gain, body length gain, body weight gain percentage, and specific growth rates compared to other treatments. Selenium concentrations in the kidney, liver, pancreas, and muscle were significantly higher (p< 0.05) in the SCE, SC, SE, and EC groups compared to the Control and single-supplement groups. Hematological parameters, including WBC, RBC, HGB, HCT, and MCHC, were significantly higher (p< 0.05) in the SCE group compared to all other groups. Similarly, serum activities of ALT, AST, and ALP were significantly lower (p< 0.05) in the SCE group than in other treatments, while blood glucose levels were unaffected (p > 0.05) by dietary treatments. Antioxidant enzyme activities, including superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx), were significantly enhanced (p< 0.05) in the whole body and muscle tissues of fish receiving Se, vitamin C, and E supplementation. Thiobarbituric acid reactive substances (TBARS) levels in muscle and serum were significantly higher (p< 0.05) in the Control group compared to all supplemented groups. The proximate composition of meat, including dry matter, fat, ash, and protein contents, was not significantly affected (p > 0.05) by the dietary treatments. In conclusion, dietary supplementation of selenium, vitamin C, and vitamin E significantly improved growth performance, selenium deposition in tissues, and antioxidant status of Hypophthalmichthys molitrix juveniles, without adversely affecting meat chemical composition.

Exploring the phytochemical profile, antioxidant activity, and anticancer potential of Achillea millefolium extracts: In-vitro and in-silico investigation - Asia Kiran; Awais Altaf; Muhammad Sarwar; Tahir Maqbool; Muhammad Abdul Basit Ashraf; Muhammad Naveed; Tariq Aziz; Metab Alharbi (South African Journal of Botany, 2025)

In-vitro and in-vivo assessments of greenly synthesized iron oxide nanoparticles from Cascabela thevetia plant extract for the treatment of ventricular septal defect - Amina Abid; Muhammad Naveed; Tariq Aziz; Muhammad Aqib Shabbir; Hira Mubeen; Ayaz Ali Khan; Abdullah F Alsmari (South African Journal of Botany, 2025)

Physio-biochemical and molecular mechanisms of low nitrogen stress tolerance in peanut (Arachis hypogaea L.) - Xiangjun Kong; Rui Wang; Peipei Jia; Hengbin Li; Aziz Khan; Ali Muhammad; Sajid Fiaz; Qunce Xing; Zhiyong Zhang (Plant Molecular Biology, 2025)

Unraveling the complexity of solitary waves in the Klein-Fock-Gordon equation: dynamical insights into bifurcation and Chaos analysis - Muhammad Moneeb Tariq; Muhammad Bilal Riaz; Muhammad Aziz ur Rehman; Dilawaiz (Modeling Earth Systems and Environment, 2025)

Effects of dietary vitamins C and E on growth performance, hematological and biochemical parameters, skeletal abnormalities, and disease resistance against V. harveyi of hybrid groupers (Epinephelus fuscoguttatus♀ × Epinephelus lanceolatus♂) - Isabella Ebi; Rossita Shapawi; Leong-Seng Lim; Annita Seok-Kian Yong; Nurzafirah Mazlan; Muhammad Dawood Shah; Najamuddin Abdul Basri; Abdul Aziz Jaziri (Aquaculture International, 2025)

Development and In-Vitro Tuning of Piperine Containing Solid Lipid Microparticles for the Treatment of Rheumatoid Arthritis - Muneeba Aziz; Sajid Bashir; Rai Muhammad Sarfraz; Hira Ijaz; Asif Mahmood; Zulcaif; Bilal Haroon; Milad A. Mezher; Mohamed M. Salem; Sami Al Zahrani; Mounir M. Bekhit (AAPS PharmSciTech, 2025)

Innovative transformation of palm oil biomass waste into sustainable biofuel: Technological breakthroughs and future prospects - Tonni Agustiono Kurniawan; Mehwish Ali; Ayesha Mohyuddin; Ahtisham Haider; Mohd Hafiz Dzarfan Othman; Abdelkader Anouzla; Hui Hwang Goh; Dongdong Zhang; Wei Dai; Faissal Aziz; Muhammad Imran Khan; Imran Ali; et al. (Process Safety and Environmental Protection, 2025)

Particle size of wheat straw from genetically improved wheat affects the production performance and feeding behavior of Sahiwal cows - Muhammad Farhan Ayaz Chishti; Muhammad Aziz ur Rahman; Muhammad Qamar Bilal; Muhammad Riaz; Muhammad Farooq Khalid; Zia-Ur-Rehman; Urooj Anwar; Riaz Mustafa; Waseem Abbas; Umar Farooq (Tropical Animal Health and Production, 2025)

Nonstationarity assessment in extreme temperatures and its association with antecedent soil moisture levels across diverse climate zones in Pakistan - Darakshan Naeem; Rizwan Aziz; Mahnoosh Moghaddasi; Ismail Yucel; Muhammad Awais (Theoretical and Applied Climatology, 2025)

Climate change projections for Diamer Division in lesser Himalayas using multi-global climate model ensemble - Didar Ahmad; Faridullah Faridullah; Muhammad Irshad; Aziz Ur Rahim Bacha; Farhan Hafeez; Akhtar Iqbal; Zahid Ullah; Muhammad Naveed Afridi; Abdulwahed Fahad Alrefaei; Rashid Nazir (Environmental Science and Pollution Research, 2024)

Systematic review on buparvaquone resistance associated with non-synonymous mutation in drug binding genes site of Theileria annulate - Muhammad Rashid; Muhammad Hassan Hayat; Naveed Zahra; Mian Sayed Khan; Suleman; Muhammad Nadeem; Tauseef ur Rehman; Muhammad Ehsan; Muhammad Irfan Malik; Muhammad Kashif Obaid; Amir Bakhsh; Mohamed Aziz Darghouth; et al. (Veterinary Parasitology, 2024)

Mitigating lead (Pb) toxicity in Zea mays (L.) plants using green synthesized iron oxide nanoparticles - Haseeba Maryam; Muhammad Rizwan; Nasir Masood; Muhammad Waseem; Temoor Ahmed; Muhammad Farooq Qayyum; Muhammad Zia-ur-Rehman; Humera Aziz (South African Journal of Botany, 2024)

Characterization of mercury ameliorating rhizobacteria for enhancing growth and yield of Triticum aestivum L. in the field: An in-vitro and in- silico study - Aatif Amin; Muhammad Naveed; Sunbul Rasheed; Zakia Latif; Tariq Aziz; Fahad Al Asmari; Maha Aljabri (South African Journal of Botany, 2024)

Chemical modification of Pinus walliichiana sawdust: Application in membrane system for efficient purification of groundwater containing Cd(II) and Ni(II) - Muhammad Imran Irfan; Mahnoor Sadiq; Lubna Zohra; Abu Bakar Siddique; Muhammad Yousaf; Madiha Rubab; Kishwar Urooj; Ambreen Aziz; Hira Ali; Mehreen Fatima; Hatem M.A. Amin; Hassan A. Alhazmi; et al. (Journal of Water Process Engineering, 2024)

Coastal urban flood risk management: Challenges and opportunities − A systematic review - Farhan Aziz; Xiuquan Wang; Muhammad Qasim Mahmood; Muhammad Awais; Bill Trenouth (Journal of Hydrology, 2024)

Wastewater flooding risk assessment for coastal communities: Compound impacts of climate change and population growth - Farhan Aziz; Xiuquan Wang; Muhammad Qasim Mahmood; Ryan Guild (Journal of Hydrology, 2024)

Catalytic pyrolysis of Padina sp. with ZSM-5 and Amberlyst-15 catalysts to produce aromatic-rich bio-oil - Apip Amrullah; Obie Farobie; Herry Irawansyah; Ismadi; Lusi Ernawati; Muhammad Aziz; Widya Fatriasari (Bioresource Technology Reports, 2024)

Integration of Local Mean Sea Level and Land Vertical Datum over Peninsular Malaysia via Transformation Model - Muhammad Faiz Pa’suya; Ami Hassan Md Din; Ramazan Alpay Abbak; Noorfatekah Talib; Mohamad Azril Che Aziz; Muhammad Zahir Ramli; Mohammad Hanif Hamden; Nornajihah Mohammad Yazid (Pure and Applied Geophysics, 2024)

Integrating MDT Tumor Board Shadowing into the Undergraduate Medical Curriculum: Perspective of Medical Students - Aasil Shayan Aziz; Masooma Shifa Rana; Salaar Ahmed; Muhammad Abdullah; Hafsa Khan Tareen; Ayesha Siddiq; Ahmed Nadeem Abbasi (Journal of Cancer Education, 2024)

A survey on the occurrence of papaya ringspot virus-P (PRSV-P) in Malaysia and genetic diversity assessment of the coat protein region - Norazyani Mohsin Mohsen; Muhamad Afiq Aziz; Kuganisha Thangaraja; Muhammad Azamuddeen Mohammad Nasir; Muhammad Zarul Hanifah Md. Zoqratt; Subha Bhassu; Rofina Yasmin Othman (Environmental Monitoring and Assessment, 2024)

Retraction Note: Assessment of Waterborne Amine-Coated Silver Nanoparticle (Ag-NP)-Induced Toxicity in Labeo rohita by Histological and Hematological Profiles - Muhammad Saleem Khan; Naureen Aziz Qureshi; Farhat Jabeen; Muhammad Shakeel; Muhammad Saleem Asghar (Biological Trace Element Research, 2024)

Comparative genomics and evolutionary analysis of dengue virus strains circulating in Pakistan - Aziz Ul-Rahman; Muhammad Zubair Shabbir; Majeeda Rasheed; Nusrat Shafi; Kalsoom AbdulRazaq; Hamna Ramzan; Rauf Mehmood; Junaid Ali Khan (Virus Genes, 2024)

A turn-on anthraquinone-derived colorimetric and fluorometric dual-mode probe for highly selective Hg2+ determination and bioimaging in living organisms - Chen Zhao; Ayesha Aziz; Wenjing Lu; Hongmei Xu; Muhammad Asif; Shaomin Shuang; Chuan Dong (Journal of Hazardous Materials, 2024)

The expanding host range of lumpy skin disease virus in wild and domestic animals - Aziz Ul-Rahman; Muhammad Zubair Shabbir; Muhammad Asif Raza; Paul Rossiter (Tropical Animal Health and Production, 2024)

The importance of sharing: wild plant knowledge in three valleys of Northern Pakistan - Adnan Ali Shah; Abid Raza; Naji Sulaiman; Dipak Khadka; Abdul Majid; Muhammad Abdul Aziz; Arshad Mehmood Abbasi; Mushtaq Ahmad; Andrea Pieroni (Plant Biosystems, 2024)

Antibacterial Efficacy of Tryptophan Coordinated Silver Nanoparticles Against E. coli: Spectroscopic and Microscopic Evaluation of Bacterial Cell Death - Rafaqat Ali Khan; Shahzad Anwar; Hina Ali; Uzma Aziz; Bisma Khanam; Muhammad Zakria; Muhammad Raffi (Journal of Fluorescence, 2024)

Tailoring tea residue-derived nitrogen-doped activated carbon for CO2 adsorption: influence of activation temperature and activating agents - Amirul Hafiiz Ruhaimi; Muhammad Arif Ab Aziz (Environmental Science and Pollution Research, 2024)

Carbon-based nanomaterials (CNMs) modified TiO2 nanotubes (TNTs) photo-driven catalysts for sustainable energy and environmental applications: A comprehensive review - Md. Arif Hossen; Riyadh Ramadhan Ikreedeegh; Azrina Abd Aziz; Abdelmoumin Yahia Zerga; Muhammad Tahir (Journal of Environmental Chemical Engineering, 2024)

Temporal characteristics of positive cloud-to-ground flashes from tropical thunderstorms - Muhammad Haziq Mohammad Sabri; Mohd Riduan Ahmad; Yuji Takayanagi; Shamsul Ammar Shamsul Baharin; Takeshi Morimoto; Zen-Ichiro Kawasaki; Mohd Zafri Baharuddin; Mohamad Zoinol Abidin Abd. Aziz; Mardina Abdullah; Vernon Cooray (Atmospheric Research, 2024)

Recent advances of MXene@MOF composites for catalytic water splitting and wastewater treatment approaches - Samreen Afzal; Aziz ur Rehman; Tayyaba Najam; Ismail Hossain; Mostafa A.I. Abdelmotaleb; Sundas Riaz; Md Rezaul Karim; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Chemosphere, 2024)

Comparative analysis of hydrogen-rich syngas production from various feedstocks using bubbling fluidized bed - Muhammad Ikhsan Taipabu; Karthickeyan Viswanathan; Vinitha Mariyappan; Po-Chih Kuo; Muhammad Aziz; Wei Wu (Process Safety and Environmental Protection, 2024)

Pluvial flood modeling for coastal areas under future climate change – A case study for Prince Edward Island, Canada - Quan Van Dau; Xiuquan Wang; Farhan Aziz; Rana Ali Nawaz; Tianze Pang; Muhammad Qasim Mahmood; Maxim Fortin (Journal of Hydrology, 2024)

Dynamic interplay of silica-coated iron oxide nanocomposite on soil-plant system to mitigate Cd toxicity in rice - Faisal Islam; Muhammad Saad Shoaib Khan; Sulaiman Ahmed; Aziz Ul Ikram; Fakhir Hannan; Mehmood Jan; Muhammad Sajid; Ali Ahmed Zaky Shoaib; Shan Liu; Jian Chen (Journal of Cleaner Production, 2024)

Synergistic interactions and reaction mechanisms of biochar surface functionalities in antibiotics removal from industrial wastewater - Muhammad Irtaza Sajjad Haider; Guijian Liu; Balal Yousaf; Muhammad Arif; Kiran Aziz; Aniqa Ashraf; Rabia Safeer; Samra Ijaz; Krzysztof Pikon (Environmental Pollution, 2024)

Light-driven C1 Chemical Conversion with LDH-based Nanomaterials - Zixi Liu; Muhammad Altaf Nazir; Muhammad Altaf; Hammad Majeed; Zeinhom M. El-Bahy; Mohamed H. Helal; Abdul Rauf; Sami Ullah; Tayyaba Najam; Syed Shoaib Ahmad Shah; Aziz ur Rehman (Applied Clay Science, 2024)

Evaluating the sustainability of groundwater abstraction in small watersheds using time series analysis - Muhammad Qasim Mahmood; Xiuquan Wang; Farhan Aziz; Tianze Pang (Groundwater for Sustainable Development, 2024)

Drivers of municipal water security and vulnerability in Pakistan: A case study of Mardan, Khyber Pakhtunkhwa - Kamran; Junaid Aziz Khan; Fasiha Safdar; Umer Khayyam; Iftikhar Hussain Adil; Abdul Waheed; Muhammad Fahim Khokhar (Groundwater for Sustainable Development, 2024)

Smartphone-assimilated colorimetric sensor for sub-nanomolar emamectin detection via KA30 capped silver nanoparticles in food, bio-fluids and water samples - Aziz Balouch; Kashif Hussain; Ayman Nafady; Abdul Jabbar; Sufian Rasheed; Sumaira Kanwal; Sadia Haider; Razium Ali Soomro; Sirajuddin; Muhammad Raza Shah (Food Chemistry, 2024)

Co-feeding biomass and municipal solid waste for enhanced hydrogen and synthetic natural gas yields employing chemical looping process - Zhuang Sun; Xiangxiang Chen; Po-Chih Kuo; Lu Ding; Muhammad Aziz (Chemical Engineering Journal, 2024)

Satellite-based rainwater harvesting sites assessment for Dera Ghazi Khan, Punjab, Pakistan - Samman Aziz; Muhammad Y. S. Dasti; Mashal Abrar; Faisal Mumtaz; Aqil Tariq (Environmental Science and Pollution Research, 2024)

Enhancing the CO2 adsorption with dual functionalized coconut shell-hydrochar using Chlorella microalgae and metal oxide: Synthesis, physicochemical properties & mechanism evaluations - Nuradila Zahirah Mohd Azmi; Archina Buthiyappan; Muhammad Fazly Abdul Patah; Nor Adilla Rashidi; Abdul Aziz Abdul Raman (Journal of Cleaner Production, 2024)

Aflatoxins in the rice production chain: A review on prevalence, detection, and decontamination strategies - Iqra Naeem; Amir Ismail; Muhammad Riaz; Mubashir Aziz; Kashif Akram; Muhammad A. Shahzad; Mavra Ameen; Sher Ali; Carlos A.F. Oliveira (Food Research International, 2024)

Hyperspectral target detection using self-supervised background learning - Muhammad Khizer Ali; Benish Amin; Abdur Rahman Maud; Farrukh Aziz Bhatti; Komal Nain Sukhia; Khurram Khurshid (Advances in Space Research, 2024)

Biodegradation of PVCs through in-vitro identification of Bacillus albus and computational pathway analysis of ABH enzyme - Muhammad Naveed; Rida Naveed; Tariq Aziz; Arooj Azeem; Mahrukh Afzal; Muhammad Waseem; Metab Alharbi; Abdulrahman Alshammari; Abdullah F. Alasmari; Thamer H. Albekairi (Biodegradation, 2024)

Kinetic exploration of CO2 methanation over nickel loaded on fibrous mesoporous silica nanoparticles (CHE-SM) - Muhammad Akmal Aziz; Aishah Abdul Jalil; Nurul Sahida Hassan; Mahadi Bin Bahari; Abdul Hakim Hatta; Tuan Amran Tuan Abdullah; Nurfatehah Wahyuny Che Jusoh; Herma Dina Setiabudi; Rajendran Saravanan (Process Safety and Environmental Protection, 2024)

Integrated study of GIS and Remote Sensing to identify potential sites for rainwater harvesting structures - Xingsheng Du; Aqil Tariq; Fakhrul Islam; Samman Aziz; Liaqat Ali Waseem; Muhammad Nasar Ahmad; Muhammad Amin; Naz Ul Amin; Shoaib Ali; Muhammad Aslam; Walid Soufan (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Progress, challenges, and prospects of MOF-based adsorbents for phosphate recovery from wastewater - Muhammad Naveed Afridi; Sawaira Adil; Battuya Byambaa; Muhammad Sohail; Aziz-Ur-Rahim Bacha; Jingwen Wang; Chaolin Li (Journal of Water Process Engineering, 2024)

Florfenicol removal from veterinary pharmaceutical effluents: Tri-metallic zeolite 5A° for electrochemical oxidation and catalytic ceramic membrane separation - Amir Ikhlaq; Maryam Gull; Afnan Sajid; Khurram Saleem Joya; Muhammad Raashid; Osama Shaheen Rizvi; Zafar Masood; Salman Ahmed; Maryam Abid; Maham Hanif; Hafiz Abdul Aziz; Thamer Abdulhameed Al Johani; et al. (Journal of Environmental Chemical Engineering, 2024)

Evaluation of drought hazards and coping strategies adopted by pastoral communities in the Cholistan Rangeland of Pakistan - Muhammad Farooq Azhar; Muhammad Junaid Faiz; Ehsan Ali; Abida Aziz; Muhammad Akbar; Ghulam Raza; Muhammad Abdullah; Muhammad Muzammil Habib; Muhammad Farooq Akram (Environmental Development, 2024)

Novel renewable seawater desalination system using hydrogen as energy carrier for self-sustaining community - Du Wen; Po-Chih Kuo; Muhammad Aziz (Desalination, 2024)

Dual fluorophores embedded in zeolitic imidazolate framework‑8 for ratiometric fluorescence sensing of a biomarker of anthrax spores - Xiaoran Zhang; Qi Wang; Xincheng Sun; Muhammad Asif; Ayesha Aziz; Yuan Zhang; Chuan Dong; Ruibing Wang; Shaomin Shuang (Chemical Engineering Journal, 2024)

Comprehensive experimental assessment of Samanea saman wood and leaves waste combustion in the aspect of ash-related problem - Suyatno Suyatno; Hafizh Ghazidin; Hanafi Prida Putra; Fairuz Milkiy Kuswa; Moch Zulfikar Eka Prayoga; Atok Setiyawan; Prabowo Prabowo; Kusmiyati Kusmiyati; Nina Konitat Supriatna; Arif Darmawan; Firman Bagja Juangsa; Muhammad Aziz; et al. (Bioresource Technology Reports, 2024)

Solar Light Assisted Metal Selenide-Chitosan Nanoparticles from Structure Tailoring to Photocatalytic Mineralization of Selected Industrial Dyes - Javeed Azam; Muhammad Farhan; Adnan Khan; Tariq Aziz; Nauman Ali; Hamayun Khan; Sumeet Malik; Nisar Ali (Water, Air, & Soil Pollution, 2024)

Long-Term Follow-Up of Cerebral Aneurysms Completely Occluded at 6 Months After Intervention with the Woven EndoBridge (WEB) Device: a Retrospective Multicenter Observational Study - Kareem El Naamani; Panagiotis Mastorakos; Nimer Adeeb; Mathews Lan; James Castiglione; Omaditya Khanna; Jose Danilo Bengzon Diestro; Rachel M. McLellan; Mahmoud Dibas; Justin E. Vranic; Assala Aslan; Hugo H. Cuellar-Saenz; et al. (Translational Stroke Research, 2024)

Evaluation of Bacillus spp. as biocontrol agents against chili leaf spot caused by Xanthomonas vesicatoria - Sadia Aziz; Saleem Akhtar Jamshed; Tariq Mukhtar; Gulshan Irshad; Shahzada Sohail Ijaz; Muhammad Usman Raja (Journal of Plant Diseases and Protection, 2024)

Investigation of heavy metals uptake in root-shoot of native plant species adjoining wastewater channels - Sardar Khyzer Bashir; Muhammad Irshad; Aziz Ur Rahim Bacha; Ping An; Faridullah Faridullah; Zahid Ullah (Environmental Monitoring and Assessment, 2024)

Application of Synthetic Iron Oxyhydroxide with Influencing Factors for Removal of As(V) and As(III) from Groundwater - Shakeel Ahmed Talpur; Muhammad Yousuf Jat Baloch; Chunli Su; Javed Iqbal; Aziz Ahmed; Hafeez Ahmed Talpur (Journal of Earth Science, 2024)

Correction to: Recent Progress in Folic Acid Detection Based on Fluorescent Carbon Dots as Sensors: A Review - Kawan F. Kayani; Mohammed K Rahim; Sewara J. Mohammed; Harez Rashid Ahmed; Muhammad S. Mustafa; Shujahadeen B. Aziz (Journal of Fluorescence, 2024)

Enantioselective dihydroxylation of xanthorrhizol from Curcuma xanthorrhiza via biotransformation using Aspergillus Niger - Nurul Iman Aminudin; Ahmad Amzar Abdul Aziz; Zaima Azira Zainal Abidin; Deny Susanti; Muhammad Taher (Natural Product Research, 2024)

Bridging biological and food monitoring: A colorimetric and fluorescent dual-mode sensor based on N-doped carbon dots for detection of pH and histamine - Xiaoran Zhang; Jing Wang; Elias Hasan; Xincheng Sun; Muhammad Asif; Ayesha Aziz; Wenjing Lu; Chuan Dong; Shaomin Shuang (Journal of Hazardous Materials, 2024)

Silicon and Titanium Dioxide Mitigate Copper Stress in Wheat (Triticum aestivum L.) Through Regulating Antioxidant Defense Mechanisms - Rana M. Alshegaihi; Muhammad Hamzah Saleem; Ammara Saleem; Baber Ali; Humera Aziz; Shah Fahad; Abed Alataway; Ahmed Z. Dewidar; Hosam O. Elansary (Journal of Plant Growth Regulation, 2024)

Trapping the genetic variation for yield and yield related attributes in bread wheat under water deficit stress - Hafiz Ghulam Muhu-Din Ahmed; Muhammad Naeem; Yawen Zeng; Aziz Ullah; Ghulam Sabir Hussain; Muhammad Irfan Akram; Amjad Saeed; Noor Fatima; Ibtasam Moeez; Hayssam M. Ali; Nagy S. Radwan; Sezai Ercisli; et al. (Euphytica, 2024)

Occurrence of toxic elements in river areas along drains and groundwater resources: source of contamination and associated health risk - Zahid Ullah; Fazila Younas; Aziz Ur Rahim Bacha; Abdur Rashid; Wedad A. Al-onazi; Muhammad Fahad Sardar (Environmental Monitoring and Assessment, 2024)

Recent Progress in Folic Acid Detection Based on Fluorescent Carbon Dots as Sensors: A Review - Kawan F. Kayani; Mohammed K Rahim; Sewara J. Mohammed; Harez Rashid Ahmed; Muhammad S. Mustafa; Shujahadeen B. Aziz (Journal of Fluorescence, 2024)

Effects of biodegradable- and non-biodegradable-rich waste separation on ash deposition behaviour during coal and refuse-derived fuel co-combustion - Adi Prismantoko; Feri Karuana; Ardi Nugroho; Puji Agus Santoso; Hanafi Prida Putra; Arif Darmawan; Muhammad Akhsin Muflikhun; Indro Pranoto; Muhammad Aziz; Hariana Hariana (Waste Management, 2024)

Giant mud crab shell biochar: A promising adsorbent for methyl violet removal in wastewater treatment - Azrul Nurfaiz Mohd Faizal; Nicky Rahmana Putra; Ahmad Hazim Abdul Aziz; Augustine Agi; Muhammad Abbas Ahmad Zaini (Journal of Cleaner Production, 2024)

Synergistic solar energy integration for enhanced biomass chemical looping hydrogen production: Thermodynamics and techno-economic analyses - Xiangxiang Chen; Zhuang Sun; Po-Chih Kuo; Muhammad Aziz (Chemical Engineering Journal, 2024)

Effect of different concentrations of resveratrol on nuclear maturation and in-vitro development competence of oocytes of Nili Ravi buffalo - Samar Wafa Kabeer; Amjad Riaz; Aziz Ul-Rahman; Rana Muhammad Shahbakht; Ahsan Anjum; Hafeez ur Rehman Ali Khera; Ali Haider; Faisal Riaz; Riffat Yasin; Muhammad Yaseen; Muhammad Saleem; Naheed Bano; et al. (Tropical Animal Health and Production, 2024)

Heritability and Genotypic Association Among Seedling Attribute Against Salinity Stress Tolerance in Wheat Genotypes for Sustainable Food Security - Hafiz Ghulam Muhu-Din Ahmed; Yawen Zeng; Xiaomeng Yang; Anns Faisal; Noor Fatima; Aziz Ullah; Ghulam Sabir Hussain; Muhammad Iftikhar; Muhammad Rizwan Anwar (Journal of Crop Health, 2024)

Assessment of historical and projected changes in extreme temperatures of Balochistan, Pakistan using extreme value theory - Darakshan Naeem; Rizwan Aziz; Muhammad Awais; Sajid Rashid Ahmad (Environmental Monitoring and Assessment, 2024)

Above-and below-ground feedback loop of maize is jointly enhanced by plant growth-promoting rhizobacteria and arbuscular mycorrhizal fungi in drier soil - Wasim Khan; Ying Zhu; Aziz Khan; Ling Zhao; Yu-Miao Yang; Ning Wang; Meng Hao; Yue Ma; Jaya Nepal; Fazal Ullah; Muhammad Maqsood Ur Rehman; Muhammad Abrar; et al. (Science of The Total Environment, 2024)

Application of manganese oxide-based materials for arsenic removal: A review - Muhammad Younas; Aziz Ur Rahim Bacha; Kaleem Khan; Iqra Nabi; Zahid Ullah; Muhammad Humayun; Jingtao Hou (Science of The Total Environment, 2024)

Unveiling the green horizon: A bibliometric analysis of global foreign direct investment research and its emphasis on climate change - Muhammad Shabbar Raza; Yusheng Wang; Abdul Rauf; Noshaba Aziz; Muhammad Ajmal Khan; Abid Hussain (Journal of Cleaner Production, 2024)

Diversity of melliferous Flora (Apiaries) in Honey and microscopic authentication using LM and SEM Techniques - Khushdil Khan; Khafsa Malik; Mushtaq Ahmad; Rahmatullah Qureshi; Muhammad Asif Aziz; Safia Gul; Wahidah H. Al-Qahtani; Raees Khan (Flora, 2024)

UV-spectrophotometric Optimization of Temperature, pH, Concentration and Time for Eucalyptus Globulus Capped Silver Nanoparticles Synthesis, their Characterization and Evaluation of Biological Applications - Ansar Aziz Subhani; Muhammad Irshad; Shaukat Ali; Muhammad Jawad; Muhammad Faran Akhtar; Muhammad Summer (Journal of Fluorescence, 2024)

Algae-derived bioactive compounds as potential pharmaceuticals for cancer therapy: A comprehensive review - Lubna Anjum Minhas; Muhammad Kaleem; Hafiz Muhammad Umer Farooqi; Farzana Kausar; Rooma Waqar; Theophilus Bhatti; Shahid Aziz; Dong Won Jung; Abdul Samad Mumtaz (Algal Research, 2024)

An Aedes–Anopheles Vaccine Candidate Supplemented with BCG Epitopes Against the Aedes and Anopheles Genera to Overcome Hypersensitivity to Mosquito Bites - Muhammad Naveed; Urooj Ali; Tariq Aziz; Rida Naveed; Sarmad Mahmood; Muhammad Mustajab Khan; Metab Alharbi; Thamer H. Albekairi; Abdullah F. Alasmari (Acta Parasitologica, 2024)

Efficient treatment of veterinary pharmaceutical industrial wastewater by catalytic ozonation process: degradation of enrofloxacin via molecular ozone reactions - Amir Ikhlaq; Zafar Masood; Umair Yaqub Qazi; Muhammad Raashid; Osama Shaheen Rizvi; Hafiz Abdul Aziz; Muhammad Saad; Fei Qi; Rahat Javaid (Environmental Science and Pollution Research, 2024)

Integrated application of biochar and chemical fertilizers improves wheat (Triticum aestivum) productivity by enhancing soil microbial activities - Muhammad Abdullah Aziz; Khalid Saifullah Khan; Rabia Khalid; Muhammad Shabaan; Abdulaziz G. Alghamdi; Zafer Alasmary; Mosaed A. Majrashi (Plant and Soil, 2024)

Efficient performance of InP and InP/ZnS quantum dots for photocatalytic degradation of toxic aquatic pollutants - Maryam Abbasi; Rukhsanda Aziz; Muhammad Tariq Rafiq; Aziz Ur Rahim Bacha; Zahid Ullah; Abdul Ghaffar; Ghulam Mustafa; Iqra Nabi; Malik Tahir Hayat (Environmental Science and Pollution Research, 2024)

Recent trends in wastewater treatment by using metal-organic frameworks (MOFs) and their composites: A critical view-point - Syed Shoaib Ahmad Shah; Manzar Sohail; Ghulam Murtza; Amir Waseem; Aziz ur Rehman; Iftikhar Hussain; Muhammad Sohail Bashir; Saleh S. Alarfaji; Ahmed M. Hassan; Muhammad Altaf Nazir; Muhammad Sufyan Javed; Tayyaba Najam (Chemosphere, 2024)

Adopting Marine Spatial Planning (MSP) using coral health assessment as indicator: A case study in Pulau Redang Marine Park, Malaysia - Farhana Razak; Wei Yien Lua; Nor Hafzan Abd Rasid; Nazli Aziz; Izarenah Md Repin; Xiong-Zhi Xue; Abdul Rahman Muhammad Ashraf; Zainudin Bachok; Aminudin Afiq-Firdaus; Wan Izatul Asma Wan Talaat; Abdul Rahman Abdul Latip; Che Din Mohd Safuan (Ocean & Coastal Management, 2024)

Retraction Note: Ameliorative effect of two structurally divergent hydrazide derivatives against DSS-induced colitis by targeting Nrf2 and NF-κB signaling in mice - Ashrafullah Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Sajjad Ahmad; Muhammad Usman Amin; Muhammad Naeem Ahmed; Zia‑ur‑Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Mutation of the VAR2 gene plays a role as one of the causes of leaf variegation in the moth orchid Phalaenopsis ‘Sogo Vivien’ - Febri Yuda Kurniawan; Saifa Usni Putri; Aviesta Linggabuwana; Muhammad Dylan Lawrie; Aziz Purwantoro; Endang Semiarti (Horticulture, Environment, and Biotechnology, 2024)

Nickel uptake in leafy greens from contaminated soil: an investigation into phytoavailability and health risk assessment using in vitro digestion model - Sumbal Ammara; Muhammad Tariq Rafiq; Rukhsanda Aziz; Ying Feng; Sultan Mehmood; Mehwish Taneez; Muhammad Suhaib; Fatima Asif (Environmental Monitoring and Assessment, 2024)

Copolymerization of ethylene and isoprene via silicon bridge metallocene [rac-Me2Si(2-Me-4-Ph-Ind)2ZrCl2] catalyst: A new way to control the composition and microstructure of copolymers - Amjad Ali; Ahmad Naveed; Anna Maroń; Muhammad Adnan Younis; Jamile Mohammadi Moradian; Balal Yousaf; Tariq Aziz; Rai Nauman Ali; Naushad Ahmad; Suliman Yousef Alomar; Fan Zheqiang; Li Guo (Chemosphere, 2024)

Engineering of metal organic framework (MOF) membrane for waste water treatment: Synthesis, applications and future challenges - Muhammad Umar Shahid; Tayyaba Najam; Mazharul Islam; Ahmed M. Hassan; Mohammed A. Assiri; Abdul Rauf; Aziz ur Rehman; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Journal of Water Process Engineering, 2024)

Deciphering the Role of Phytohormones and Osmolytes in Plant Tolerance Against Salt Stress: Implications, Possible Cross-Talk, and Prospects - Sadam Hussain; Muhammad Bilal Hafeez; Rabia Azam; Kashf Mehmood; Marjan Aziz; Sezai Ercisli; Talha Javed; Ali Raza; Noreen Zahra; Saddam Hussain; Xiaolong Ren (Journal of Plant Growth Regulation, 2024)

Biochemical profile of Vaucheria karachiensis and evaluation of its nutritional, antioxidant, antimicrobial, and hypoglycemic potentials - Arshad Iqbal; Muhammad Imran; Syed Lal Badshah; Ashwag Shami; Baber Ali; Zamarud Shah; Muhammad Ayaz; Abdulrahman Alasmari; Marzough Aziz Albalawi; Amin A. Al-Doaiss; Majed A. Bajaber; Sezai Ercisli (Algal Research, 2024)

HPLC-DAD, GC–MS, UHPLC-Q-TOF/MS2, ICP-MS and FT-NIR combined with the chemometrics explain seasonal variation in Cassia senna L. leaves from the coast of Red Sea in Sudan - Haroon Elrasheid Tahir; Sulafa B.H. Hashim; Muhammad Arslan; Gustav Komla Mahunu; Huang Xiaowei; Li Zhihua; Abdalbasit Adam Mariod; Isameldeen I.H. Abdalla; Hesham R. El-Seedi; Ahmed Abdel Aziz Ahmed; Zou Xiaobo (South African Journal of Botany, 2023)

Protecting coastal tourism through developing tourists' environment responsible behaviour - Sadia Aziz; Muhammad Abdullah Khan Niazi (Journal of Outdoor Recreation and Tourism, 2023)

Valorization of Momordica charantia seeds into phytogenically synthesized silver nanoparticles for the protection of oyster mushrooms against Trichoderma pleuroticola - Norhidayah Abd Aziz; Noor Hasyierah Mohd Salleh; Subash Chandra Bose Gopinath; Azlina Harun Kamaruddin; Muhammad Izzat Ridzuan; Nurul Afiqah Ahmad (Journal of Environmental Chemical Engineering, 2023)

Synthesis and characterization of nanobiochar from rice husk biochar for the removal of safranin and malachite green from water - Sadia Aziz; Bushra Uzair; Muhammad Ishtiaq Ali; Sundas Anbreen; Fatiha Umber; Muneeba Khalid; Alaa AA. Aljabali; Yachana Mishra; Vijay Mishra; Ángel Serrano-Aroca; Gowhar A. Naikoo; Mohamed El-Tanani; et al. (Environmental Research, 2023)

Correction to: The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Developing Micropropagation Protocols of Date Palm (Phoenix dactylifera L.) cv. Barhi Using Shoot Tip Explants - Najamuddin Solangi; Adel Ahmed Abul-Soad; Mushtaque Ahmed Jatoi; Ghulam Sarwar Markhand; Muhammad Aslam Solangi; Abdul Aziz Mirani (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2023)

Molecular characterization of lumpy skin disease virus from recent outbreaks in Pakistan - Shumaila Manzoor; Muhammad Abubakar; Aziz Ul-Rahman; Zainab Syed; Khurshid Ahmad; Muhammad Afzal (Archives of Virology, 2023)

Socio- and techno-economic analyses of biodiesel production from sewage sludge in Tokyo, Japan - Muhammad Usman; Shuo Cheng; Sasipa Boonyubol; Muhammad Aziz; Jeffrey S. Cross (Journal of Cleaner Production, 2023)

Tackling microplastics pollution in global environment through integration of applied technology, policy instruments, and legislation - Tonni Agustiono Kurniawan; Ahtisham Haider; Ayesha Mohyuddin; Rida Fatima; Muhammad Salman; Anila Shaheen; Hafiz Muhammad Ahmad; Hussein E. Al-Hazmi; Mohd Hafiz Dzarfan Othman; Faissal Aziz; Abdelkader Anouzla; Imran Ali (Journal of Environmental Management, 2023)

Solubilization and Uptake of Phosphorus (P) by Wheat and Maize Crops from Indigenous Rock Phosphate Applied with Biogas Slurry and Bagasse Ash - Ammara Farooq; Bushra Saeed; Hafiz Muhammad Bilal; Muhammad Aamer Maqsood; Muhammad Nasim; Tariq Aziz; Minggang Xu (Water, Air, & Soil Pollution, 2023)

Retraction Note: Inhibition of NF-κB signaling and HSP70/HSP90 proteins by newly synthesized hydrazide derivatives in arthritis model - Ashraf Ullah Khan; Amna Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Muhammad Naeem Ahmed; Salman Ul Islam; Hussain Ali; Adeeb Shehzad; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Emerging trends of green hydrogen and sustainable environment in the case of Australia - Afifa Qadeer; Muhammad Wasim Hussan; Ghazala Aziz; Rida Waheed; Suleman Sarwar (Environmental Science and Pollution Research, 2023)

Elucidating growth and biochemical characteristics of rice seedlings under stress from chromium VI salt and nanoparticles - Maryam Noor; Arif Ullah; Muhammad Israr Khan; Irum Raza; Muhammad Iqbal; Abdul Aziz; Gil Won Kim; Nadia Taimur; Azizullah Azizullah; Imran Ali; Pil Joo Kim (Environmental Science and Pollution Research, 2023)

Foliar architecture differentially restrains metal sequestration capacity in wheat grains (Triticum aestivum L.) grown in hyper-chloride-contaminated soils - Muhammad Sajid Aqeel Ahmad; Mansoor Hameed; Muhammad Kaleem; Sana Fatima; Farooq Ahmad; Muhammad Farooq; Mehtab Maratib; Iqra Aziz (Environmental Science and Pollution Research, 2023)

Nanosheet arrays of iron oxide for enhanced ammonia synthesis via electrochemical nitrogen reduction for prospective algal membrane bioreactors - Muhammad Adnan Younis; Saira Manzoor; Amjad Ali; Fazal Haq; Tariq Aziz; Mehwish Kiran; Arshad Farid; Mohamed E. El Sayed; Mohammad N. Murshed; Zeinhom M. El-Bahy; Muhammad Saeed Akhtar (Chemosphere, 2023)

Titanium doped cobalt ferrite fabricated graphene oxide nanocomposite for efficient photocatalytic and antibacterial activities - Kiran Khalid; Anam Zahra; Umay Amara; Muhammad Khalid; Muhammad Hanif; Mubashir Aziz; Khalid Mahmood; Muhammad Ajmal; Muhammad Asif; Kinza Saeed; Muhammad Farooq Qayyum; Waseem Abbas (Chemosphere, 2023)

Could climate change exacerbate droughts in Bangladesh in the future? - Mahfuzur Rahman; Md Sakib Hasan Tumon; Md Monirul Islam; Ningsheng Chen; Quoc Bao Pham; Kashif Ullah; Sumaiya Jarin Ahammed; Sharmina Naznin Liza; Md Abdul Aziz; Salit Chakma; Muhammad Esmat Enan; Md. Alomgir Hossain; et al. (Journal of Hydrology, 2023)

Effects of micro(nano)plastics on soil nutrient cycling: State of the knowledge - Muhammad Salam; Huaili Zheng; Yingying Liu; Aneeqa Zaib; Syed Aziz Ur Rehman; Nimra Riaz; Moataz Eliw; Faisal Hayat; Hong Li; Fayuan Wang (Journal of Environmental Management, 2023)

Reaction kinetics study in direct chemical looping process based on a multi-step reaction scheme - Zhuang Sun; Lu Ding; Po-Chih Kuo; Muhammad Aziz (Fuel, 2023)

Occurrence, source identification and ecological risk assessment of heavy metals in water and sediments of Uchalli lake – Ramsar site, Pakistan - Ayesha Aftab; Rukhsanda Aziz; Abdul Ghaffar; Muhammad Tariq Rafiq; Ying Feng; Zafeer Saqib; Muhammad Khalid Rafiq; Muhammad Akbar Awan (Environmental Pollution, 2023)

Synthesis of MXene-based single-atom catalysts for energy conversion applications - Muhammad Aizaz Ud Din; Syed Shoaib Ahmad Shah; Muhammad Sufyan Javed; Manzar Sohail; Aziz ur Rehman; Muhammad Altaf Nazir; Mohammed A. Assiri; Tayyaba Najam; Nanpu Cheng (Chemical Engineering Journal, 2023)

The effects of cultivation type and maturity stage on arsenic species concentration and carrageenan content in Kappaphycus spp. from Semporna, Sabah - Ghanthimathi Subramaniam; Noumie Surugau; Nor Azwady Abd Aziz; Radhiah Shukri; Kharidah Muhammad (Journal of Applied Phycology, 2023)

Adsorptive and photocatalytic degradation potential of porous polymeric materials for removal of pesticides, pharmaceuticals, and dyes-based emerging contaminants from water - Azeem Intisar; Arooj Ramzan; Shahzar Hafeez; Nazim Hussain; Muhammad Irfan; Nasir Shakeel; Komal Aziz Gill; Amjad Iqbal; Marcin Janczarek; Teofil Jesionowski (Chemosphere, 2023)

A multi-period design method for the steam and power systems coupling solar thermal energy and waste heat recovery in refineries - Jing Wang; Lixia Kang; Yongzhong Liu; Muhammad Aziz (Journal of Cleaner Production, 2023)

Comparative immunocompetence and interspecies transmission of avian orthoavulavirus-1 in feral birds originating from rural and urban settings - Momena Habib; Aziz Ul-Rahman; Zia-ur-Rehman; Muhammad Akbar Shahid; Noreen Sarwar; Muhammad Bilal; Muhammad Saeed Imran; Muhammad Munir; Shaista Abbas; Muhammad Zubair Shabbir (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Effect of additives in increasing ash fusion temperature during co-firing of coal and palm oil waste biomass - Hariana Hariana; Hafizh Ghazidin; Arif Darmawan; Edi Hilmawan; Prabowo; Muhammad Aziz (Bioresource Technology Reports, 2023)

Interactions of Metal‐Based Engineered Nanoparticles with Plants: An Overview of the State of Current Knowledge, Research Progress, and Prospects - Abdul Wahab; Asma Munir; Muhammad Hamzah Saleem; Mukhtar Iderawumi AbdulRaheem; Humera Aziz; Manar Fawzi Bani Mfarrej; Gholamreza Abdi (Journal of Plant Growth Regulation, 2023)

The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Assessment of heavy metals and associated oxidative stress in occupationally exposed workers from Bannu and Karak Districts in Pakistan - Kaleem Khan; Muhammad Tariq Rafiq; Aziz-Ur-Rahim Bacha; Iqra Nabi; Muhammad Irshad; Faridullah Faridullah; Muhammad Younas; Muhammad Daud Khan; Rukhsanda Aziz; Muhammad Amin; Awais Arifeen; Sohaib Aslam; et al. (Environmental Geochemistry and Health, 2023)

Progress in the utilization of water hyacinth as effective biomass material - Asep Bayu Dani Nandiyanto; Risti Ragadhita; Siti Nur Hofifah; Dwi Fitria Al Husaeni; Dwi Novia Al Husaeni; Meli Fiandini; Senny Luckiardi; Eddy Soeryanto Soegoto; Arif Darmawan; Muhammad Aziz (Environment, Development and Sustainability, 2023)
Water hyacinth ( Eichhornia crassipes ) is considered a prospective free-floating aquatic plant potentially used to address current issues on food, energy, and the environment. It can grow quickly and easily in various tropical and subtropical environments as long as it has access to adequate light and water to support photosynthetic growth. Ecosystems are threatened by their invasive growth and remarkable capacity for adaptation. However, managing this plant can result in valuable products. This paper demonstrates particle technologies that might be used to utilize water hyacinths, including brake pads, fertilizer, bioenergy, animal feed, phytoremediation agents, bioplastics, and adsorbents. This study is accompanied by a discussion based on the conducted experiments and currently available literature, providing readers with a clearer understanding. Water hyacinth's capacity to absorb macro- and micro-nutrients, nitrogen, and phosphorus makes it a good plant for phytoremediation. The prospect of producing cellulose makes it prospective as a biomass energy source and livestock feeding. Further, it can be transformed into high-cellulose content particles for applications in bioplastics, brake pads, and adsorbents. The current reports regarding education of water hyacinth to student also were added. Finally, issues and suggestions for future development related to the use of water hyacinths are discussed. This study is expected to provide comprehensive knowledge on how to turn invasive water hyacinth plants into valuable products.

Efficient conversion of waste-to-SNG via hybrid renewable energy systems for circular economy: Process design, energy, and environmental analysis - Po-Chih Kuo; Biju Illathukandy; Zhuang Sun; Muhammad Aziz (Waste Management, 2023)

Geotechnical properties of problematic expansive subgrade stabilized with guar gum biopolymer - Muhammad Hamza; Zhihong Nie; Mubashir Aziz; Nauman Ijaz; Chuanfeng Fang; Muhammad Usman Ghani; Zain Ijaz; Sadaf Noshin; Muhammad Salman (Clean Technologies and Environmental Policy, 2023)

Process design, simulation, and techno-economic analysis of integrated production of furfural and glucose derived from palm oil empty fruit bunches - Muhammad Zafran Raja Mohammed; Zi Wei Ng; Aditya Putranto; Zong Yang Kong; Jaka Sunarso; Muhammad Aziz; Sharif H. Zein; Jannata Giwangkara; Ivan Butar (Clean Technologies and Environmental Policy, 2023)

Temporal study of wastewater surveillance from September 2020 to March 2021: an estimation of COVID-19 patients in Lahore, Pakistan - Muhammad Adnan Ashraf; Muhammad Nawaz; Ali Asif; Muhammad Asad Ali; Adnan Mehmood; Muhammad Waqar Aziz; Muhammad Zubair Shabbir; Nadia Mukhtar; Muhammad Abu Bakr Shabbir; Sohail Raza; Tahir Yaqub (Environmental Science and Pollution Research, 2023)

On the pursuit of emissions-free clean mobility – Electric vehicles versus e-fuels - Sai Sudharshan Ravi; Chris Brace; Charles Larkin; Muhammad Aziz; Felix Leach; James WG Turner (Science of The Total Environment, 2023)

Islamic corporate sustainability practices index aligned with SDGs towards better financial performance: Evidence from the Malaysian and Indonesian Islamic banking industry - Amin Jan; Haseeb Ur Rahman; Muhammad Zahid; Anas A. Salameh; Parvez Alam Khan; Mamdouh Abdulaziz Saleh Al-Faryan; Roslizawati Binti Che Aziz; H. Elhosiny Ali (Journal of Cleaner Production, 2023)

A crucial review on the challenges and recent gas membrane development for biogas upgrading - Nur Fajrina; Norhaniza Yusof; Ahmad Fauzi Ismail; Farhana Aziz; Muhammad Roil Bilad; Meshel Alkahtani (Journal of Environmental Chemical Engineering, 2023)

CO2 utilization in chemical looping gasification and co-gasification of lignocellulosic biomass components over iron-based oxygen carriers: Thermogravimetric behavior, synergistic effect, and reduction characteristics - Po-Chih Kuo; Zhuang Sun; Faruk Özdemir; Muhammad Aziz; Wei Wu (Journal of Environmental Chemical Engineering, 2023)

Evaluation of haematological, serum biochemical and oxidative stress parameters in cattle naturally infected with lumpy skin disease virus - Aziz Ul-Rahman; Muhammad Furqan Shahid; Muhammad Zahid Iqbal; Aijaz Ali Channa; Majeeda Rasheed; Muhammad Adnan; Rauf Mahmood; Hafiz Muhammad Ishaq; Hafeez ur Rehman Ali Khera; Kashif Hussain; Muhammad Asif Raza (Tropical Animal Health and Production, 2023)

A review of research trends on the usage of photocatalysis for wastewater treatment: bibliometric analysis - Abdussamad Mukhtar Mohammed; Farhana Aziz; Safia Syazana Mohtar; Shakhawan Ahmad Mhamad; Bello Ahmadu; Mustapha Usman Nasir; Khuzaifa Yahuza Muhammad; Madzlan Aziz (Sustainable Water Resources Management, 2023)

Zinc oxide nanoparticles coated urea enhances nitrogen efficiency and zinc bioavailability in wheat in alkaline calcareous soils - Shaiza Amin; Tariq Aziz; Muhammad Zia-ur-Rehman; Ifra Saleem; Muhammad Rizwan; Ambreen Ashar; Hafiz Adnan Mussawar; Muhammad Aamer Maqsood (Environmental Science and Pollution Research, 2023)

Synthesis, characterization and adsorption behavior of modified cellulose nanocrystals towards different cationic dyes - Tariq Aziz; Arshad Farid; Sampath Chinnam; Fazal Haq; Mehwish Kiran; Ab Waheed Wani; Zeid A. Alothman; Ahmed Muteb Aljuwayid; Mohamed A. Habila; Muhammad Saeed Akhtar (Chemosphere, 2023)

Long-term manure application increased soil organic carbon and nitrogen mineralization through accumulation of unprotected and physically protected carbon fractions - Muhammad Nadeem ASHRAF; Cheng HU; Xiangru XU; Tariq AZIZ; Lei WU; Muhammad Ahmed WAQAS; Muhammad FAROOQ; Xu HU; Wenju ZHANG; Minggang XU (Pedosphere, 2023)

Imaging Lowstand prograding stratigraphic pinch-out traps of a Lower Cretaceous clastic system using inverted seismic-based porosity simulation of SE-Asian Basin: Implications for petroleum exploration - Muhammad Tayyab Naseer; Shazia Naseem; Dyana Aziz Bayz (Marine and Petroleum Geology, 2023)

H2 impact on combustion kinetics, soot formation, and NOx emission of hydrocarbon fuel flames - M. Zuhaib Akram; Fanhua Ma; Muhammad Aziz; Yangbo Deng; Han Wu (Fuel, 2023)

Challenges associated with cellulose composite material: Facet engineering and prospective - Tariq Aziz; Fazal Haq; Arshad Farid; Mehwish Kiran; Shah Faisal; Asmat Ullah; Naveed Ullah; Awais Bokhari; Muhammad Mubashir; Lai Fatt Chuah; Pau Loke Show (Environmental Research, 2023)

Role of silica-based porous cellulose nanocrystals in improving water absorption and mechanical properties - Tariq Aziz; Arshad Farid; Fazal Haq; Mehwish Kiran; Naveed Ullah; Shah Faisal; Amjad Ali; Farman Ullah Khan; Siming You; Awais Bokhari; Muhammad Mubashir; Lai Fatt Chuah; et al. (Environmental Research, 2023)

Wild food plants gathered by four cultural groups in North Waziristan, Pakistan - Noor Khalid; Lal Badshah; Adnan Ali Shah; Arman Ullah; Naushad Khan; Muhammad Abdul Aziz; Renata Sõukand; Andrea Pieroni (Genetic Resources and Crop Evolution, 2023)

Permeability modeling of Upper Cretaceous Bahariya Formation rocks, Abu Sennan field, Western Desert, Egypt - Hesham Hassan Abuseda; Abdel Moktader Abdel Aziz El Sayed; Osama Muhammad Elnaggar (Arabian Journal of Geosciences, 2023)
The present work aims to describe in detail the petrophysical properties of the Bahariya Formation (Abu Sennan field) through processing the core sample data and finding out the possible relations between permeability and other reservoir parameters such as porosity, specific internal surface, formation factor, and nuclear magnetic resonance to obtain reliable permeability prediction model of the Upper Cretaceous formation. The core samples have a length range of 2–4 cm with a diameter of 2.54 cm. Many petrophysical reservoir parameters were measured, such as permeability, porosity, density, formation factor, and special measurements such as spectral induced polarization, nuclear magnetic resonance, and specific internal surface. The samples cover a wide range of porosity (11.82–23.68 %) and permeability (0.06–133.65 mD). The porosity-permeability relationship indicates the increase of the permeability with porosity increase for the studied samples. The reservoir quality index ranges from 0.02 to 0.78 μm. The flow zone indicator ranges from 0.09 to 3.39 μm where pore throat radius ( R 35 ) ranges from 0.10 to 7.40 μm. The reservoir quality index (RQI) and flow zone indicator (FZI) cross-plot show a better understanding of the formation evaluation. The hydraulic flow units are (0.09 μm T 1 range is 1.21–175 ms, NMR transversal relaxation time T 2(100) range is 0.70–91.77 ms, and T 2(600) range is 0.74–75.86 ms. Models that incorporate porosity and NMR relaxation times will be more accurate and suitable for permeability prediction. Using multiple regression to determine the exponents of the power-law equation and replacing the porosity with the formation factor can improve the permeability prediction for the samples under investigation. The utilizing of NMR in predicting the permeability through a robust model considers an additional value for the Upper Cretaceous rocks in Egypt.

Biodegradation of macro- and micro-plastics in environment: A review on mechanism, toxicity, and future perspectives - Aziz-Ur-Rahim Bacha; Iqra Nabi; Muhammad Zaheer; Wenbiao Jin; Lei Yang (Science of The Total Environment, 2023)

The versatility of nanocellulose, modification strategies, and its current progress in wastewater treatment and environmental remediation - Ajmal Shahzad; Muhammad Wajid Ullah; Jawad Ali; Kazim Aziz; Muhammad Asif Javed; Zhijun Shi; Sehrish Manan; Mazhar Ul-Islam; Mudasir Nazar; Guang Yang (Science of The Total Environment, 2023)

Techno-economic analysis of PV systems installed by using innovative strategies for smart sustainable agriculture farms - Yahya Aziz; Abdul Kashif Janjua; Muhammad Hassan; Mustafa Anwar; Saira Kanwal; Muhammad Yousif (Environment, Development and Sustainability, 2023)

3-D quantitative seismic imaging of tectonically-influenced Middle-Eocene carbonates stratigraphic traps of SE-Asian basins using spectral decomposition: Implications for hydrocarbon exploration - Muhammad Tayyab Naseer; Shazia Naseem; Dyana Aziz Bayz (Journal of Applied Geophysics, 2023)

RETRACTED: Investigation on synthesis of ternary g-C3N4/ZnO–W/M nanocomposites integrated heterojunction II as efficient photocatalyst for environmental applications - Misbah Malik; Thomas Len; Rafael Luque; Sameh M. Osman; Emilia Paone; Muhammad Imran Khan; Muhammad Ahmad Wattoo; Muhammad Jamshaid; Aqsa Anum; Aziz ur Rehman (Environmental Research, 2023)

Efficient photocatalytic degradation of Rhodamine B dye using solar light-driven La˗Mn co-doped Fe2O3 nanoparticles - Sobia Maqbool; Adeel Ahmed; Arif Mukhtar; Muhammad Jamshaid; Aziz Ur Rehman; Saima Anjum (Environmental Science and Pollution Research, 2023)

Insight into microwave-assisted synthesis of the chitosan-MOF composite: Pb(II) adsorption - Humaira Gul Zaman; Lavania Baloo; Shamsul Rahman Kutty; Khalid Aziz; Muhammad Altaf; Aniqa Ashraf; Faissal Aziz (Environmental Science and Pollution Research, 2023)

Empirical relationship between creativity and carbon intensity: a case of OPEC countries - Ghazala Aziz; Suleman Sarwar; Muhammad Shahbaz; Muhammad Nasir Malik; Rida Waheed (Environmental Science and Pollution Research, 2022)

Reducing environmental pollution by organisational citizenship behaviour in hospitality industry: the role of green employee involvement, performance management and dynamic capability - Ataul Karim Patwary; Arshian Sharif; Roslizawati Che Aziz; Mohamad Ghozali Bin Hassan; Arsalan Najmi; Muhammad Khalilur Rahman (Environmental Science and Pollution Research, 2022)

Sedimentological and diagenetic analysis of Early Eocene Margalla Hill Limestone, Shahdara area, Islamabad, Pakistan: implications for reservoir potential - Haroon Aziz; Jabir Hussain; Muhammad Tariq; Muhsan Ehsan; Salman Khurshid; Saleem Khan; Waleed Anwar (Carbonates and Evaporites, 2022)

Biomonitoring of mercury in water, sediments, and fish (brown and rainbow trout) from remote alpine lakes located in the Himalayas, Pakistan - Javed Nawab; Junaid Ghani; Syed Aziz Ur Rehman; Muhammad Idress; Muhammad Luqman; Sardar Khan; Ali Asghar; Ziaur Rahman (Environmental Science and Pollution Research, 2022)

Strengthening potential of xanthan gum biopolymer in stabilizing weak subgrade soil - Muhammad Hamza; Zhihong Nie; Mubashir Aziz; Nauman Ijaz; Zain Ijaz; Zia ur Rehman (Clean Technologies and Environmental Policy, 2022)

RETRACTED ARTICLE: Ameliorative effect of two structurally divergent hydrazide derivatives against DSS-induced colitis by targeting Nrf2 and NF-κB signaling in mice - Ashrafullah Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Sajjad Ahmad; Muhammad Usman Amin; Muhammad Naeem Ahmed; Zia-ur-Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Hybrid geoid model over peninsular Malaysia (PMHG2020) using two approaches - Muhammad Faiz Pa’suya; Ami Hassan Md Din; Ramazan Alpay Abbak; Mohammad Hanif Hamden; Nornajihah Mohammad Yazid; Mohamad Azril Che Aziz; Mohd Adhar Abd Samad (Studia Geophysica et Geodaetica, 2022)

Nutritional Value of Dry Fish in Bangladesh and Its Potential Contribution to Addressing Malnutrition: A Narrative Review - Md. Hasan Al Banna; Abdullah Al Zaber; Nahidur Rahman; Md Abrar Mozahid Siddique; Muhammad Abu Bakr Siddique; John Elvis Hagan; M. A. Rifat; Christiana Naa Atsreh Nsiah-Asamoah; Abdul-Aziz Seidu; Bright Opoku Ahinkorah; Md Shafiqul Islam Khan (Fishes, 2022)
Understanding the linkage between the nutrient composition of foods and individuals’ recommended nutrient intake is important to address malnutrition. Despite it being a traditional and popular food item in Bangladesh, the nutrient composition of dry fish has not been reviewed yet. This study used a narrative review to assess the nutrient composition of dry fish and estimated its potential contribution to addressing some common nutritional deficiencies among children and pregnant and lactating women in Bangladesh. Records were collected from different databases, including the Web of Science, Google Scholar, PubMed, ScienceDirect, Banglajol, and ResearchGate. Data were extracted from 48 articles containing 1128 entries regarding nutrient composition. Most of the nutrient analyses estimated the proximate composition, whereas vitamin, mineral, amino acid, and fatty acid compositions were scarce in the literature. We found that dry fish has high protein and mineral content and could contribute highly to meeting the recommended nutrient intake of protein, iron, zinc, and calcium for children and pregnant and lactating women. The summarized nutrient composition data could be useful for further research to observe how dry fish could be best utilized to address malnutrition in Bangladesh. This narrative review recommends that further nutrient analysis, with emphasis on vitamin, mineral, and fatty acid compositions.

Effect of forage to concentrate ratio on growth performance and feeding behavior of Thalli lambs - Muhammad Farhan Ayaz Chishti; Muhammad Aziz ur Rahman; Karamo Jatta; Sajjad Khan; Muhammad Riaz; Qamar Bilal; Urooj Anwar; Sibtain Ahmad; Hassan Munir Bajwa; Fahd Rasul (Tropical Animal Health and Production, 2022)

Design considerations of variable rate liquid fertilizer applicator for mature oil palm trees - Muhammad Yamin; Wan Ishak bin Wan Ismail; Samsuzana Abd Aziz; Muhamad Saufi bin Mohd Kassim; Farah Naz Akbar; Muhammad Ibrahim (Precision Agriculture, 2022)

Pyroptosis in acute pancreatitis and its therapeutic regulation - Abdullah Al Mamun; Suzia Aktar Suchi; Md. Abdul Aziz; Muhammad Zaeem; Fahad Munir; Yanqing Wu; Jian Xiao (Apoptosis, 2022)

The nexus between traditional foraging and its sustainability: a qualitative assessment among a few selected Eurasian case studies - Muhammad Abdul Aziz; Giulia Mattalia; Naji Sulaiman; Adnan Ali Shah; Zbynek Polesny; Raivo Kalle; Renata Sõukand; Andrea Pieroni (Environment, Development and Sustainability, 2022)

Sargassum wightii Aqueous Extract Improved Salt Stress Tolerance in Abelmoschus esculentus by Mediating Metabolic and Ionic Rebalance - Zawar Khan; Humaira Gul; Mamoona Rauf; Muhammad Arif; Muhammad Hamayun; Aziz Ud-Din; Zahoor Ahmad Sajid; Sheza Ayaz Khilji; Aliya Rehman; Asma Tabassum; Zahida Parveen; In-Jung Lee (Frontiers in Marine Science, 2022)
Salinity stress has hindered the growth and yield of crops globally. The demands for inducing salt stress tolerance by natural and biological sources with potent antioxidants and growth-promoting metabolites have been the main focus of the recent era. Therefore, the current research was conducted to extract salt stress tolerance-ameliorating metabolites and growth-promoting hormones from the marine brown macroalgae Sargassum wightii Greville ex J. Agardh with maximum antioxidant potential used as a liquid fertilizer for okra ( Abelmoschus esculentus L.). In the current study, the biochemical analysis showed that Sargassum aqueous extract (SAE) was rich in growth-promoting metabolites, antioxidants, and hormones. Meanwhile, overaccumulation of glycine betaine attracted the focus of the current research dealing with salt stress tolerance amelioration in A. esculentus . The plants supplemented with SAE (2% and 4%) and 0.04% ascorbic acid (AsA) alone and in combinations were subjected to sodium salt stress (NaCl; 75 mM). Results revealed that SAE efficiently promoted the vegetative and reproductive growth of plants by elevating the growth-promoting metabolites and hormones in comparison to control plants. Ionic contents (Na + , K + , Ca 2+ , and Mg 2+ ) and ratios (K + /Na + , Mg 2+ /Na + , and Ca 2+ /Na + ) were modulated in SAE-treated plants. SAE also increased the level of carbohydrates, proteins, lipids, carotenoids, and proline and decreased the level of hydrogen peroxide and abscisic acid in salt-treated plants compared with the control groups. Enzymatic activities of catalase, ascorbate peroxidase, and guaiacol peroxidase were also enhanced by SAE treatment upon salt stress. The SAE-mediated stress tolerance amelioration and the positive growth response of A. esculentus were further accelerated by AsA (0.04%) supplementation used in combination with SAE (2% and 4%). The current study revealed a novel report of the antioxidant and metabolite-rich algal extract ( S. wightii ) formulation along with AsA that induced salt stress tolerance and promoted the overall growth performance of A. esculentus by rebalancing the ionic and metabolic status.

Repressors: the gatekeepers of phytohormone signaling cascades - Usman Aziz; Muhammad Saad Rehmani; Lei Wang; Baoshan Xian; Xiaofeng Luo; Kai Shu (Plant Cell Reports, 2022)

Organic geochemical and petrological evaluation to assess the remaining hydrocarbon potential and depositional conditions: a case study of the Paleozoic shales of west Perlis region, northern Peninsular Malaysia - Muhammad Nadzmi Abdul Ghofur; Jasmi Hafiz Abdul Aziz; Yousif M. Makeen; Wan Hasiah Abdullah; Mohammed Hail Hakimi (Arabian Journal of Geosciences, 2022)

Strategic combination of metal–organic frameworks and C3N4 for expeditious photocatalytic degradation of dye pollutants - Ome Parkash Kumar; Muhammad Ahmad; Muhammad Altaf Nazir; Aqsa Anum; Muhammad Jamshaid; Syed Shoaib Ahmad Shah; Aziz Rehman (Environmental Science and Pollution Research, 2022)

Impact of different nitrogen management options and weed competition periods on weed dynamics, productivity, and profitability of bread wheat - Muhammad Saqib; Abdul Khaliq; Asif Tanveer; Tariq Aziz (Arabian Journal of Geosciences, 2022)

Strengthening of high plastic clays by geotextile reinforcement - Muhammad Hamza; Mubashir Aziz; Wang Xiang; Muhammad Waqas Younis; Zhihong Nie; Muhammad Ali; Mudassar Dilawar; Ashiru Mohammed; Farhad Ali; Rahat Ullah; Mazhar Yasin; Atteq Ur Rehman (Arabian Journal of Geosciences, 2022)

Compositional Quality and Possible Gastrointestinal Performance of Marketed Probiotic Supplements - Ghazal Aziz; Arsalan Zaidi; Muhammad Tariq (Probiotics and Antimicrobial Proteins, 2022)

Prevalence, epidemiology, seasonality, and phylogeny of Anaplasma marginale in blood samples of goats collected from Punjab, Pakistan - Muhammad Naveed Aziz; Muhammad Irfan; Asia Parveen; Muhammad Asif; Maryam Ijaz; Sadia Mumtaz; Sezayi Ozubek; Munir Aktas; Rana Khalid Iqbal; Furhan Iqbal (Tropical Animal Health and Production, 2022)

Isatin derivatives as broad-spectrum antiviral agents: the current landscape - Tilal Elsaman; Malik Suliman Mohamed; Eyman Mohamed Eltayib; Hatem A. Abdel-aziz; Abualgasim Elgaili Abdalla; Muhammad Usman Munir; Magdi Awadalla Mohamed (Medicinal Chemistry Research, 2022)

Climatology of dust storm frequency and its association with temperature and precipitation patterns over Pakistan - Mehwish Aziz Dar; Rehan Ahmed; Muhammad Latif; Muhammad Azam (Natural Hazards, 2022)

Spatio-temporal variability of drought characteristics across Pakistan - Jae Eun Lee; Muhammad Azam; Saif Ur Rehman; Muhammad Waseem; M. Naveed Anjum; Arslan Afzal; M. J. M. Cheema; Muhammad Mehtab; Muhammad Latif; Rehan Ahmed; Muhammad Umar; Abid Sarwar; et al. (Paddy and Water Environment, 2022)

Soil microbial biomass and extracellular enzyme–mediated mineralization potentials of carbon and nitrogen under long-term fertilization (> 30 years) in a rice–rice cropping system - Muhammad Nadeem Ashraf; Gao Jusheng; Wu Lei; Adnan Mustafa; Ahmed Waqas; Tariq Aziz; Waqas-ud-Din Khan; Shafeeq-ur-Rehman; Babar Hussain; Muhammad Farooq; Zhang Wenju; Xu Minggang (Journal of Soils and Sediments, 2021)

Role of pine wilt disease based on optimal control strategy at multiple scales: A case study of Korea - Muhammad Ozair; Takasar Hussain; Kashif Ali Abro; Sajid Jameel; Aziz Ullah Awan (Journal of Biosciences, 2021)

Essential oil composition and antibacterial activity of Canarium strictum Roxb. resin - Halima Tahir; Nadeem Muhammad; Azeem Intisar; Muhammad Imran Din; Uzma Qaisar; Muhammad Abdul Qadir; Noor Ul Ain; Zeeshan Ahmad; Pakeeza Aziz; Muhammad Khurram Shahzad; Irshad Hussain (Plant Biosystems, 2021)

Constituents and antibacterial activity of leaf essential oil of Plectranthus scutellarioides - Pakeeza Aziz; Nadeem Muhammad; Azeem Intisar; Muhammad Amin Abid; Muhammad Imran Din; Muhammad Yaseen; Rehana Kousar; Aqsa Aamir; Quratulain; Rabia Ejaz (Plant Biosystems, 2021)

Correction to: Health risk assessment of hexachlorocyclohexane in soil, water and plants in the agricultural area of Potohar region, Punjab, Pakistan - Talat Ara; Waqar-Un Nisa; Rukhsanda Aziz; Muhammad Tariq Rafiq; Rafaqat Ali Gill; Malik Tahir Hayat; Uzma Afridi (Environmental Geochemistry and Health, 2021)

Copper Nanoparticles as Growth Promoter, Antioxidant and Anti-Bacterial Agents in Poultry Nutrition: Prospects and Future Implications - Muhammad Sharif; Muhammad Aziz-ur Rahman; Bilal Ahmed; Rao Zahid Abbas; Faiz-ul Hassan (Biological Trace Element Research, 2021)

Determination of pesticide residues in dates using UHPLC-QqQ-MS/MS: method development and validation - Somia Qayyum; Touqeer Taj; Muhammad Tauseef; Muhammad Ishtiaq; Nazia Rafique; Karam Ahad; Muhammad Aslam Mirza; Muhammad Aziz Choudhary; Farrakh Mehboob (Environmental Monitoring and Assessment, 2021)

Health risk assessment of hexachlorocyclohexane in soil, water and plants in the agricultural area of Potohar region, Punjab, Pakistan - Talat Ara; Waqar-Un Nisa; Rukhsanda Aziz; Muhammad Tariq Rafiq; Rafaqat Ali Gill; Malik Tahir Hayat; Uzma Afridi (Environmental Geochemistry and Health, 2021)

An in vitro antiviral activity of iodine complexes against SARS-CoV-2 - Imran Altaf; Muhammad Faisal Nadeem; Nadir Hussain; Muhammad Nawaz; Sohail Raza; Muhammad Abu bakr Shabbir; Muhammad Adnan Ashraf; Muhammad Asad Ali; Sohail Hassan; Muhammad Waqar Aziz; Nazish Matti; Muhammad Ashraf; et al. (Archives of Microbiology, 2021)

Achieving pro-poor growth and environmental sustainability agenda through information technologies: as right as rain - Muhammad Imran; Khan Burhan Khan; Khalid Zaman; Mohammed Borhandden Musah; Elih Sudiapermana; Abdul Rashid Abdul Aziz; Rahimah Embong; Zainudin Bin Hassan; Mohd Khata Jabor; Siti Nisrin Mohd Anis (Environmental Science and Pollution Research, 2021)

Catalytic transformation of Brassica nigra oil into biodiesel using in-house engineered green catalyst: Development and characterization - Ushna Fatima; Farooq Ahmad; Muhammad Ramzan; Saba Aziz; Muhammad Tariq; Hafiz M. N. Iqbal; Muhammad Imran (Clean Technologies and Environmental Policy, 2021)

RETRACTED ARTICLE: Inhibition of NF-κB signaling and HSP70/HSP90 proteins by newly synthesized hydrazide derivatives in arthritis model - Ashraf Ullah Khan; Amna Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Muhammad Naeem Ahmed; Salman Ul Islam; Hussain Ali; Adeeb Shehzad; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

A review on nanofluid water alternating gas (N-WAG): application, preparation, mechanism, and challenges - Hassan Aziz; Temoor Muther; Muhammad Jawad Khan; Fahad I. Syed (Arabian Journal of Geosciences, 2021)

Mitigating Drought Stress in Sunflower (Helianthus annuus L.) Through Exogenous Application of β-Aminobutyric Acid - Allah Wasaya; Tanveer Abbas; Tauqeer Ahmad Yasir; Naeem Sarwar; Ahsan Aziz; Muhammad Mansoor Javaid; Sheeraz Akram (Journal of Soil Science and Plant Nutrition, 2021)

Drought Tolerance Strategies in Plants: A Mechanistic Approach - Muhammad Ilyas; Mohammad Nisar; Nadeem Khan; Ali Hazrat; Aamir Hamid Khan; Kashif Hayat; Shah Fahad; Aziz Khan; Abid Ullah (Journal of Plant Growth Regulation, 2021)

Metataxonomic analysis of microbiota from Pakistani dromedary camelids milk and characterization of a newly isolated Lactobacillus fermentum strain with probiotic and bio-yogurt starter traits - Kanwal Aziz; Zubair Farooq; Muhammad Tariq; Arsalan Haseeb Zaidi (Folia Microbiologica, 2021)

Synthesis, characterization, antimicrobial, antioxidant and computational evaluation of N-acyl-morpholine-4-carbothioamides - Hamid Aziz; Aamer Saeed; Muhammad Aslam Khan; Shakeeb Afridi; Farukh Jabeen (Molecular Diversity, 2021)

Biomonitoring of Toxic Metals in Feathers of Birds from North-Eastern Pakistan - Bushra Aziz; Muhammad Zubair; Nausheen Irshad; Khawaja Shafique Ahmad; Majid Mahmood; Majid Mahmood Tahir; Khizar Hussain Shah; Aqeela Shaheen (Bulletin of Environmental Contamination and Toxicology, 2021)
The current study was designed to determine the concentrations of toxic metals (Ni, Pb and Cr) in feathers of birds collected from four regions of NE Pakistan. Feather samples of birds (House Crow, Common Myna and House Sparrow) were collected from different areas. Atomic absorption spectrophotometer was used to determine the concentration of metals in feathers. Analysis of the data revealed that concentrations of Pb and Cr were significantly different ( p < 0.05) among bird species, whereas no difference ( p > 0.05) was detected among bird species (house crow, common myna and house sparrow) for Ni. A significant difference was found for the concentration of Pb and Ni in all the four studied regions. Whereas, non-significant difference was found in all the studied regions for the concentrating of Cr. It was revealed that there is significant rising concentration of metals (Pb, Cr) in feathers of birds in Azad Kashmir.

Foliage applied potassium improves stay green, photosynthesis and yield of maize (Zea mays L.) under rainfed condition - Allah Wasaya; Tauqeer Ahmad Yasir; Naeem Sarwar; Omer Farooq; Atique ur Rehman; Khuram Mubeen; Muqarrab Ali; Muhammad Affan; Ahsan Aziz (Plant Physiology Reports, 2021)

Investigating the impact of injection-water salinity and well strategies on water mobility and oil production in an oil-wet reservoir - Muhammad Jawad Khan; Temoor Muther; Hassan Aziz; Muhammad Mubeen-ur-Rehman (Modeling Earth Systems and Environment, 2021)

Depositional, diagenetic, and sequence stratigraphic constrains on reservoir characterization: a case study of middle Jurassic Samana Suk Formation, western Salt Range, Pakistan - Bilal Wadood; Mansoor Aziz; Junaid Ali; Nasar Khan; Jamal Wadood; Ahmad Khan; Muhammad Shafiq; Mohib Ullah (Journal of Sedimentary Environments, 2021)

Effect of plant spacing on incidence of rice planthoppers in transplanted rice crop - Muhammad Asghar; Talfoor-ul Hassan; Muhammad Arshad; Asif Aziz; Muhammad Tahir Latif; Arshed Makhdoom Sabir (International Journal of Tropical Insect Science, 2021)

Carbon, nitrogen, and phosphorus stoichiometry mediate sensitivity of carbon stabilization mechanisms along with surface layers of a Mollisol after long-term fertilization in Northeast China - Muhammad Mohsin Abrar; Hu Xu; Tariq Aziz; Nan Sun; Adnan Mustafa; Muhammad Wajahat Aslam; Syed Atizaz Ali Shah; Khalid Mehmood; Baoku Zhou; Xingzhu Ma; Xianni Chen; Minggang Xu (Journal of Soils and Sediments, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

A comparative phylogenomic analysis of SARS-CoV-2 strains reported from non-human mammalian species and environmental samples - Aziz Ul-Rahman; Muhammad Abu Bakr Shabbir; Muhammad Waqar Aziz; Saima Yaqub; Asif Mehmood; Muhammad Asif Raza; Muhammad Zubair Shabbir (Molecular Biology Reports, 2020)

Chemical fractionation and risk assessment of trace elements in sewage sludge generated from various states of Pakistan - Umair Riaz; Ghulam Murtaza; Saifullah; Muhammad Farooq; Humera Aziz; Ayesha Abdul Qadir; Shahzada Munawar Mehdi; Muhammad Akram Qazi (Environmental Science and Pollution Research, 2020)

Characterizing Lentil Germplasm for Zinc Biofortification and High Grain Output - Naser Rasheed; Muhammad Aamer Maqsood; Tariq Aziz; Abdul Jabbar (Journal of Soil Science and Plant Nutrition, 2020)

Response surface methodology and artificial neural network for remediation of acid orange 7 using TiO2-P25: optimization and modeling approach - Muhammad Zulfiqar; Sujan Chowdhury; Abdul Aziz Omar; Ahmer Ali Siyal; Suriati Sufian (Environmental Science and Pollution Research, 2020)

Enhanced bioremediation of diesel range hydrocarbons in soil using biochar made from organic wastes - Sadia Aziz; Muhammad Ishtiaq Ali; Uzma Farooq; Asif Jamal; Fang-Jing Liu; Huan He; Hongguang Guo; Michael Urynowicz; Zaixing Huang (Environmental Monitoring and Assessment, 2020)

Correction to: Sublethal effects of a juvenile hormone analog, Pyriproxyfen demographic parameters of non-target predator, Hippodamia convergens Guerin-Meneville (Coleoptera: Coccinellidae) - Ayesha Iftikhar; Faisal Hafeez; Muhammad Hafeez; Muhammad Farooq; Muhammad Asif Aziz; Muhammad Sohaib; Afifa Naeem; Yaobin Lu (Ecotoxicology, 2020)

Sublethal effects of a juvenile hormone analog, Pyriproxyfen on demographic parameters of non-target predator, Hippodamia convergens Guerin-Meneville (Coleoptera: Coccinellidae) - Ayesha Iftikhar; Faisal Hafeez; Muhammad Hafeez; Muhammad Farooq; Muhammad Asif Aziz; Muhammad Sohaib; Afifa Naeem; Yaobin Lu (Ecotoxicology, 2020)

The nexus of environmental degradation and technology innovation and adoption: an experience from dragon - Wang Xinmin; Peng Hui; Muhammad Hafeez; Babar Aziz; Muhammad Waqas Akbar; Muhammad Ayzed Mirza (Air Quality, Atmosphere & Health, 2020)

Soil and microbial biomass stoichiometry regulate soil organic carbon and nitrogen mineralization in rice-wheat rotation subjected to long-term fertilization - Muhammad Nadeem Ashraf; Cheng Hu; Lei Wu; Yinghua Duan; Wenju Zhang; Tariq Aziz; Andong Cai; Muhammad Mohsin Abrar; Minggang Xu (Journal of Soils and Sediments, 2020)

A comparative evaluation of serum biochemistry profile and antigenic relatedness among velogenic and mesogenic Avian avulavirus 1 infection in chickens and pigeons - Aziz Ul-Rahman; Muhammad Abu Bakr Shabbir; Mushtaq Ahmed; Muhammad Zubair Shabbir (Tropical Animal Health and Production, 2020)

Influence of Crapemyrtle aphid, Tinocallis kahawaluokalani (Hemiptera: Aphididae) on population characteristics of three aphidophagous ladybird beetles - Muhammad Asif Aziz; Habiba Sadaf; Ayesha Iftikhar; Faisal Hafeez (International Journal of Tropical Insect Science, 2020)

An Integrated Systems Biology and Network-Based Approaches to Identify Novel Biomarkers in Breast Cancer Cell Lines Using Gene Expression Data - Abbas Khan; Zainab Rehman; Huma Farooque Hashmi; Abdul Aziz Khan; Muhammad Junaid; Abrar Mohammad Sayaf; Syed Shujait Ali; Fakhr Ul Hassan; Wang Heng; Dong-Qing Wei (Interdisciplinary Sciences: Computational Life Sciences, 2020)

Extracting mass concentration time series features for classification of indoor and outdoor atmospheric particulates - Lal Hussain; Wajid Aziz; Sharjil Saeed; Muhammad Rafique; Malik Sajjad Ahmed Nadeem; Seong-O Shim; Sania Aftar; Jawad-ur-Rehman Pirzada (Acta Geophysica, 2020)

Impact of urbanization, economic growth, and population size on residential carbon emissions in the SAARC countries - Muhammad Khalid Anser; Majed Alharthi; Babar Aziz; Sarah Wasim (Clean Technologies and Environmental Policy, 2020)

Effect of biochars, biogenic, and inorganic amendments on dissolution and kinetic release of phytoavailable silicon in texturally different soils under submerged conditions - Muhammad Irfan Sohail; Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali; Muhammad Ashar Ayub; Tariq Aziz; Muhammad Saqib; Ghulam Murtaza (Arabian Journal of Geosciences, 2020)

Characterization of a novel cotton MYB gene, GhMYB108-like responsive to abiotic stresses - Abid Ullah; Muhammad Tahir Ul Qamar; Mohammad Nisar; Ali Hazrat; Gul Rahim; Aamir Hamid Khan; Kashif Hayat; Saeed Ahmed; Waqar Ali; Aziz khan; Xiyan Yang (Molecular Biology Reports, 2020)

The role of garlic oil in the amelioration of oxidative stress and tissue damage in rohu Labeo rohita treated with silver nanoparticles - Muhammad Saleem Khan; Naureen Aziz Qureshi; Farhat Jabeen; Muhammad Wajid; Sabeen Sabri; Muhammad Shakir (Fisheries Science, 2020)

Lipids as biomarkers of brain disorders - Ghulam Hussain; Haseeb Anwar; Azhar Rasul; Ali Imran; Muhammad Qasim; Shamaila Zafar; Muhammad Imran; Syed Kashif Shahid Kamran; Nimra Aziz; Aroona Razzaq; Waseem Ahmad; Asghar Shabbir; et al. (Critical Reviews in Food Science and Nutrition, 2020)

Response of growth, antioxidant enzymes and root exudates production towards As stress in Pteris vittata and in Astragalus sinicus colonized by arbuscular mycorrhizal fungi - Liu Yizhu; Muhammad Imtiaz; Allah Ditta; Muhammad Shahid Rizwan; Muhammad Ashraf; Sajid Mehmood; Omar Aziz; Fathia Mubeen; Muhammad Ali; Nosheen Noor Elahi; Raina Ijaz; Sha Lele; et al. (Environmental Science and Pollution Research, 2020)

Detection of QTLs for outcrossing-related traits in rice (Oryza sativa L.) by association mapping and the RSTEP-LRT method - Lal Bux; Dalu Li; Muhammad Faheem; Ognigamal Sowadan; Zhiyao Dong; Erbao Liu; Mehtab Ali; Yanhui Li; Helder Manuel Sitoe; Abdul Aziz Mirani; Delin Hong (Euphytica, 2019)

Overview performance of lanthanide oxide catalysts in methanation reaction for natural gas production - Salmiah Jamal Mat Rosid; Susilawati Toemen; Malik Muhammad Asif Iqbal; Wan Azelee Wan Abu Bakar; Wan Nur Aini Wan Mokhtar; Md Maniruzzaman A. Aziz (Environmental Science and Pollution Research, 2019)

DNA barcoding of Haplophyllum gilesii (Hemsel.) C. C. Townsend from the Gilgit-Baltistan Province of Pakistan - Bushra Khan; Habib Ahmad; Jan Alam; Muhammad Shahid Nadeem; Aziz Ud-Din; Inam Ullah; Shafee Ur Rehman; Khushi Muhammad (Brazilian Journal of Botany, 2019)

Circulation of multiple subtypes (A, G and CRFs 02_AG) of human immunodeficiency virus type 1 (HIV-1) in selected districts of Punjab province, Pakistan - Saima Yaqub; Tahir Yaqub; Muhammad Zubair Shabbir; Asif Nadeem; Nadia Mukhtar; Firnas Ata Ur Rehman; Aziz-ul Rahman; Muhammad Furqan Shahid; Muzaffar Ali; Tayyebah Sohail; Zarfishan Tahir (Archives of Virology, 2019)

Phytotoxic analysis of coastal medicinal plants and quantification of phenolic compounds using HPLC - Muhammad Qasim; Yoshiharu Fujii; Muhammad Zaheer Ahmed; Irfan Aziz; Kazuo N. Watanabe; M. Ajmal Khan (Plant Biosystems, 2019)

A comparative phylogenomic analysis of peste des petits ruminants virus isolated from wild and unusual hosts - Aziz-ul- Rahman; Muhammad Munir; Muhammad Zubair Shabbir (Molecular Biology Reports, 2019)

A comparative genomic and evolutionary analysis of circulating strains of Avian avulavirus 1 in Pakistan - Aziz-ul Rahman; Muhammad Munir; Muhammad Zubair Shabbir (Molecular Genetics and Genomics, 2019)

An empirical evaluation of financial development-carbon footprint nexus in One Belt and Road region - Muhammad Hafeez; Chunhui Yuan; Khuram Shahzad; Babar Aziz; Kashif Iqbal; Salman Raza (Environmental Science and Pollution Research, 2019)

A comparative phylogenomic analysis of avian avulavirus 1 isolated from non-avian hosts: conquering new frontiers of zoonotic potential among species - Aziz Ul-Rahman; Muhammad Zubair Shabbir (Archives of Virology, 2019)

Variants in KIAA0825 underlie autosomal recessive postaxial polydactyly - Irfan Ullah; Naseebullah Kakar; Isabelle Schrauwen; Shabir Hussain; Imen Chakchouk; Khurram Liaqat; Anushree Acharya; Naveed Wasif; Regie Lyn P. Santos-Cortez; Saadullah Khan; Abdul Aziz; Kwanghyuk Lee; et al. (Human Genetics, 2019)

Integrated use of biochar and compost to improve soil microbial activity, nutrient availability, and plant growth in arid soil - Muhammad Akmal; Zubaira Maqbool; Khalid Saifullah Khan; Qaiser Hussain; Shahzada Sohail Ijaz; Muhammad Iqbal; Irfan Aziz; Amjad Hussain; Muhammad Subtain Abbas; Hafeez Ullah Rafa (Arabian Journal of Geosciences, 2019)

Effect of poultry litter biochar on chromium (Cr) bioavailability and accumulation in spinach (Spinacia oleracea) grown in Cr-polluted soil - Adiba Khan Sehrish; Rukhsanda Aziz; Muhammad Mazhar Hussain; Muhammad Tariq Rafiq; Muhammad Rizwan; Niaz Muhammad; Muhammad Khalid Rafiq; Anum Sehar; Jalal ud Din; Mohammad I. Al-Wabel; Shafaqat Ali (Arabian Journal of Geosciences, 2019)

Peste des petits ruminants in wild ungulates - Aziz-ul-Rahman; Jonas Johansson Wensman; Muhammad Abubakar; Muhammad Zubair Shabbir; Paul Rossiter (Tropical Animal Health and Production, 2018)

Biochar for sustainable soil and environment: a comprehensive review - Niaz Muhammad; Mubashir Hussain; Waheed Ullah; Taj Ali Khan; Shafaqat Ali; Ali Akbar; Rukhsanda Aziz; Muhammad Khalid Rafiq; Robert Thomas Bachmann; Mohammad I. Al-Wabel; Muhammad Rizwan (Arabian Journal of Geosciences, 2018)

Sesbagrandiflorain A and B: isolation of two new 2-arylbenzofurans from the stem bark of Sesbania grandiflora - Noviany Noviany; Arif Nurhidayat; Sutopo Hadi; Tati Suhartati; Muhammad Aziz; Neny Purwitasari; Iman Subasman (Natural Product Research, 2018)

Ameliorative Effects of Selenium in ZnO NP-Induced Oxidative Stress and Hematological Alterations in Catla catla - Muhammad Saleem Asghar; Naureen Aziz Qureshi; Farhat Jabeen; Muhammad Saleem Khan; Muhammad Shakeel; Abdul Shakoor Chaudhry (Biological Trace Element Research, 2018)

Synthesis of biochar from sugarcane filter-cake and its impacts on physiological performance of lettuce (Lettuce sativa) grown on cadmium contaminated soil - Anum Sehar; Rukhsanda Aziz; Muhammad Tariq Rafiq; Muhammad Mazhar Hussain; Muhammad Rizwan; Adiba Khan Sehrish; Muhammad Khalid Rafiq; Jalal ud Din; Qaiser Hussain; Mohammad I. Al-Wabel; Shafaqat Ali (Arabian Journal of Geosciences, 2018)

Influence of organic and inorganic passivators on Cd and Pb stabilization and microbial biomass in a contaminated paddy soil - Saqib Bashir; Muhammad Shaaban; Qaiser Hussain; Sajid Mehmood; Jun Zhu; Qingling Fu; Omar Aziz; Hongqing Hu (Journal of Soils and Sediments, 2018)

Genomic and biological characterization of Newcastle disease viruses isolated from migratory mallards (Anas platyrhynchos) - Momena Habib; Tahir Yaqub; Jawad Nazir; Wasim Shehzad; Aziz-ul-Rahman; Tayyebah Sohail; Nadia Mukhtar; Arsalan Mehboob; Muhammad Munir; Muhammad Zubair Shabbir (Archives of Virology, 2018)

Riverine flood assessment in Jhang district in connection with ENSO and summer monsoon rainfall over Upper Indus Basin for 2010 - Bushra Khalid; Bueh Cholaw; Débora Souza Alvim; Shumaila Javeed; Junaid Aziz Khan; Muhammad Asif Javed; Azmat Hayat Khan (Natural Hazards, 2018)

Correction to: Increasing water productivity, nitrogen economy, and grain yield of rice by water saving irrigation and fertilizer-N management - Omar Aziz; Saddam Hussain; Muhammad Rizwan; Muhammad Riaz; Saqib Bashir; Lirong Lin; Sajid Mehmood; Muhammad Imran; Rizwan Yaseen; Guoan Lu (Environmental Science and Pollution Research, 2018)

Increasing water productivity, nitrogen economy, and grain yield of rice by water saving irrigation and fertilizer-N management - Omar Aziz; Saddam Hussain; Muhammad Rizwan; Muhammad Riaz; Saqib Bashir; Lirong Lin; Sajid Mehmood; Muhammad Imran; Rizwan Yaseen; Guoan Lu (Environmental Science and Pollution Research, 2018)

Analysis of chloroplast differences in leaves of rice isonuclear alloplasmic lines - Danfeng Tang; Fan Wei; Muhammad Haneef Kashif; Aziz Khan; Zengqiang Li; Qiqi Shi; Ruixing Jia; Hongying Xie; Li Zhang; Bin Li; Peng Chen; Ruiyang Zhou (Protoplasma, 2018)

Ag@MnxOy: an effective catalyst for photo-degradation of rhodamine B dye - Muhammad Saeed; Aziz Ahmad; Rajender Boddula; Inamuddin; Atta ul Haq; Aisha Azhar (Environmental Chemistry Letters, 2018)

RETRACTED ARTICLE: Assessment of Waterborne Amine-Coated Silver Nanoparticle (Ag-NP)-Induced Toxicity in Labeo rohita by Histological and Hematological Profiles - Muhammad Saleem Khan; Naureen Aziz Qureshi; Farhat Jabeen; Muhammad Shakeel; Muhammad Saleem Asghar (Biological Trace Element Research, 2018)

Comparative Effects of Biochar, Slag and Ferrous–Mn Ore on Lead and Cadmium Immobilization in Soil - Sajid Mehmood; Muhammad Rizwan; Saqib Bashir; Allah Ditta; Omar Aziz; Li Zhe Yong; Zhihua Dai; Muhammad Akmal; Waqas Ahmed; Muhammad Adeel; Muhammad Imtiaz; Shuxin Tu (Bulletin of Environmental Contamination and Toxicology, 2018)

Radiation efficiency and nitrogen fertilizer impacts on sunflower crop in contrasting environments of Punjab, Pakistan - Wajid Nasim; Ashfaq Ahmad; Asad Amin; Muhammad Tariq; Muhammad Awais; Muhammad Saqib; Khawar Jabran; Ghulam Mustafa Shah; Syeda Refat Sultana; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Muhammad Zaffar Hashmi; et al. (Environmental Science and Pollution Research, 2018)

Pcal_0632, a phosphorylating glyceraldehyde-3-phosphate dehydrogenase from Pyrobaculum calidifontis - Iram Aziz; Naeem Rashid; Raza Ashraf; Masood Ahmed Siddiqui; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2018)

Nitrogen nutrition in cotton and control strategies for greenhouse gas emissions: a review - Aziz Khan; Daniel Kean Yuen Tan; Fazal Munsif; Muhammad Zahir Afridi; Farooq Shah; Fan Wei; Shah Fahad; Ruiyang Zhou (Environmental Science and Pollution Research, 2017)

Nitrogen fertility and abiotic stresses management in cotton crop: a review - Aziz Khan; Daniel Kean Yuen Tan; Muhammad Zahir Afridi; Honghai Luo; Shahbaz Atta Tung; Mir Ajab; Shah Fahad (Environmental Science and Pollution Research, 2017)

Structural and functional characteristics of plant proteinase inhibitor-II (PI-II) family - Shazia Rehman; Ejaz Aziz; Wasim Akhtar; Muhammad Ilyas; Tariq Mahmood (Biotechnology Letters, 2017)

Pcal_0111, a highly thermostable bifunctional fructose-1,6-bisphosphate aldolase/phosphatase from Pyrobaculum calidifontis - Iram Aziz; Naeem Rashid; Raza Ashraf; Qamar Bashir; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2017)

Eco-Friendly Synthesis of Silver Nanoparticles Through Economical Methods and Assessment of Toxicity Through Oxidative Stress Analysis in the Labeo Rohita - Muhammad Saleem Khan; Naureen Aziz Qureshi; Farhat Jabeen; Muhammad Saleem Asghar; Muhammad Shakeel; Muhammad Fakhar -e -Alam (Biological Trace Element Research, 2017)

Optimizing the phosphorus use in cotton by using CSM-CROPGRO-cotton model for semi-arid climate of Vehari-Punjab, Pakistan - Asad Amin; Wajid Nasim; Muhammad Mubeen; Muhammad Nadeem; Liaqat Ali; Hafiz Mohkum Hammad; Syeda Refat Sultana; Khawar Jabran; M. Habib ur Rehman; Shakeel Ahmad; Muhammad Awais; Atta Rasool; et al. (Environmental Science and Pollution Research, 2017)

Bioaccumulation of heavy metals and analysis of mineral element alongside proximate composition in foot, gills and mantle of freshwater mussels (Anodonta anatina) - Muhammad Sohail; Muhammad Naeem Khan; Abdul Shakoor Chaudhry; Naureen Aziz Qureshi (Rendiconti Lincei. Scienze Fisiche e Naturali, 2016)

Pcal_1127, a highly stable and efficient ribose-5-phosphate pyrophosphokinase from Pyrobaculum calidifontis - Tahira Bibi; Sumera Perveen; Iram Aziz; Qamar Bashir; Naeem Rashid; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2016)

A new fatty acid ester from an edible mushroom Rhizopogon luteolus - Gülsen Tel-Çayan; Akhtar Muhammad; Mehmet Emin Duru; Mehmet Öztürk; Achyut Adhikari; Aziz Türkoğlu (Natural Product Research, 2016)

RETRACTED ARTICLE: Toxic Effects of Titanium Dioxide Nanoparticles and Titanium Dioxide Bulk Salt in the Liver and Blood of Male Sprague-Dawley Rats Assessed by Different Assays - Muhammad Shakeel; Farhat Jabeen; Naureen Aziz Qureshi; Muhammad Fakhr-e-Alam (Biological Trace Element Research, 2016)

Allelopathic potential of oil seed crops in production of crops: a review - Adnan Noor Shah; Javaid Iqbal; Abid Ullah; Guozheng Yang; Muhammad Yousaf; Shah Fahad; Mohsin Tanveer; Waseem Hassan; Shahbaz Atta Tung; Leishan Wang; Aziz Khan; Yingying Wu (Environmental Science and Pollution Research, 2016)

Fatty acid compositional changes during the embryonic development of the swimming crab, Portunus pelagicus (Portunidae: Decapoda) - Nicholas Romano; Muhammad Asyraf Safee; Mahdi Ebrahimi; Aziz Arshad (Invertebrate Reproduction & Development, 2016)

Wheat Allergy and Intolerence; Recent Updates and Perspectives - Imran Pasha; Farhan Saeed; Muhammad Tauseef Sultan; Rizwana Batool; Mahwash Aziz; Waqas Ahmed (Critical Reviews in Food Science and Nutrition, 2016)

Effects of in situ habitat quality and landscape characteristics in the oil palm agricultural matrix on tropical understory birds, fruit bats and butterflies - Badrul Azhar; Chong Leong Puan; Najjib Aziz; Muhammad Sainuddin; Nurfatin Adila; Sohaimi Samsuddin; Siti Asmah; Muhamad Syafiq; Syafiq A. Razak; Ahmad Hafizuddin; Ainil Hawa; Syari Jamian (Biodiversity and Conservation, 2015)

The use of PCR technique in the identification of Mycobacterium species responsible for bovine tuberculosis in cattle and buffaloes in Pakistan - Farah Akhtar; Muhammad Tariq Javed; Aziz-ur-Rehman; Muhammad Nisar Khan; Pervez Akhtar; Sayed Misdaq Hussain; Muhammad Sohaib Aslam; Razia Kausar; Mehwish Qamar; Monica Cagiola (Tropical Animal Health and Production, 2015)

Accumulation of mercury in rice grain and cabbage grown on representative Chinese soils - Chun-fa Liu; Cheng-xian Wu; Muhammad T. Rafiq; Rukhsanda Aziz; Dan-di Hou; Zhe-li Ding; Zi-wen Lin; Lin-jun Lou; Yuan-yuan Feng; Ting-qiang Li; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Responses of energy balance, physiology, and production for transition dairy cows fed with a low-energy prepartum diet during hot season - Huawei Su; Yachun Wang; Qian Zhang; Fuwei Wang; Zhijun Cao; Muhammad Aziz Ur Rahman; Binghai Cao; Shengli Li (Tropical Animal Health and Production, 2013)

Deterministic and probabilistic seismic hazard analysis for Gwadar City, Pakistan - Shafiq Ur Rehman; Muhammad Khalid; Asif Ali; Abd El-aziz Khairy Abd El-Aal (Arabian Journal of Geosciences, 2013)

Pathological speech signal analysis and classification using empirical mode decomposition - Muhammad Kaleem; Behnaz Ghoraani; Aziz Guergachi; Sridhar Krishnan (Medical & Biological Engineering & Computing, 2013)

Ranging and foraging of Himalayan grey langurs (Semnopithecus ajax) in Machiara National Park, Pakistan - Riaz Aziz Minhas; Usman Ali; Muhammad Siddique Awan; Khawaja Basharat Ahmed; Muhammad Nasim Khan; Naeem Iftikhar Dar; Qamar Zaman Qamar; Hassan Ali; Cyril C. Grueter; Yamato Tsuji (Primates, 2013)

A Parametric Study on Stability of Open Excavations in Alluvial Soils of Lahore District, Pakistan - Muhammad Irfan; Aziz Akbar; Mubashir Aziz; Ammad Hassan Khan (Geotechnical and Geological Engineering, 2013)

Antioxidant and lipoxygenase inhibiting new iridoid glucosides from Caryopteris odorata - Tayyaba Shahzadi; Muhammad Athar Abbasi; Aziz Ur-Rehman; Tauheeda Riaz; Khalid Mohammed Khan; Muhammad Ashraf; Iftikhar Afzal; Muhammad Nadeem Akhtar; Muhammad Ajaib (Natural Product Research, 2013)

Zinc nutrition in rice production systems: a review - Hafeez-ur Rehman; Tariq Aziz; Muhammad Farooq; Abdul Wakeel; Zed Rengel (Plant and Soil, 2012)

Biofortification and estimated human bioavailability of zinc in wheat grains as influenced by methods of zinc application - Shahid Hussain; Muhammad Aamer Maqsood; Zed Rengel; Tariq Aziz (Plant and Soil, 2012)

Assessment of radiological hazard of NORM in Margalla Hills limestone, Pakistan - Muhammad Ali; Aziz Ahmed Qureshi; Abdul Waheed; Muzahir Ali Baloch; Hamza Qayyum; Muhammad Tufail; Hameed Ahmed Khan (Environmental Monitoring and Assessment, 2012)

Assessment of background levels of trace metals in water and soil from a remote region of Himalaya - Munir H. Shah; Javed Iqbal; Nazia Shaheen; Nadeem Khan; Muhammad Aziz Choudhary; Gulraiz Akhter (Environmental Monitoring and Assessment, 2012)

Synthesis, characterization, and urease inhibition of 5-substituted-8-methyl-2H-pyrido[1,2-a]pyrimidine-2,4(3H)-diones - Abdul Rauf; Sumaira Liaqat; Ashfaq M. Qureshi; Muhammad Yaqub; Aziz U. Rehman; Mahmood U. Hassan; Zahid H. Chohan; Faiz U. H. Nasim; T. Ben Hadda (Medicinal Chemistry Research, 2012)

Evaluating surface drying and re-drying for wheat seed priming with polyamines: effects on emergence, early seedling growth and starch metabolism - Muhammad Farooq; Tariq Aziz; Hafeez ur Rehman; Atique ur Rehman; Sardar Alam Cheema; Tariq Aziz (Acta Physiologiae Plantarum, 2011)

Study of heritable variation and genetics of earliness in mungbean (Vigna radiata L. Wilczek) - Aziz ur Rehman; Muhammad Amjad Ali; Muhammad Saleem; W. Tadesse (Euphytica, 2010)

Serum Electrolyte and Mineral Variations During Pregnancy and Lactation in Nili-Ravi Buffalo - M. Saleem Akhtar; Abdul Asim Farooq; Syed Aun Muhammad; Laeeq Akbar Lodhi; C. Sikandar Hayat; M. Mushtaq Aziz (Biological Trace Element Research, 2010)

Phylogeny and phylogeography of critically endangered Gyps species based on nuclear and mitochondrial markers - Muhammad Arshad; Javier Gonzalez; Abdel Aziz El-Sayed; Tim Osborne; Michael Wink (Journal of Ornithology, 2009)

Monoterpene glycosides from Indigofera hetrantha - Sajid Mehmood; Aziz-Ur-Rahman; Zaheer Ahmad; Nighat Afza; Abdul Malik; Habib Ahmad; Muhammad Iqbal Choudhary (Natural Product Research, 2008)

Studies on the chemical constituents of Phyllanthus emblica - Habib-ur-Rehman; Khawaja Ansar Yasin; Muhammad Aziz Choudhary; Naeem Khaliq; Atta-ur-Rahman; Muhammad Iqbal Choudhary; Shahid Malik (Natural Product Research, 2007)

The effect of surface profile, rock strength and pretension load on bending behaviour of fully grouted bolts - Hossein Jalalifar; Naj Aziz; Muhammad Hadi (Geotechnical and Geological Engineering, 2006)

Complexity analysis of stride interval time series by threshold dependent symbolic entropy - Wajid Aziz; Muhammad Arif (European Journal of Applied Physiology, 2006)

Effect of seedling age and water depth on morphological and physiological aspects of transplanted rice under high temperature - Abdul Aziz Khakwani; Masaaki Shiraishi; Muhammad Zubair; Mohammad Safdar Baloch; Khalid Naveed; Inayatullah Awan (Journal of Zhejiang University-SCIENCE B, 2005)